Coating film, composite member, golf club, fishing rod, touch panel, solar cell, helmet, rotary body and moving body

JP2025042239APending Publication Date: 2025-03-27HARDOLASS HLDG CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023149125
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-14
Publication Date
2025-03-27

Smart Images

  • Figure 2025042239000001_ABST
    Figure 2025042239000001_ABST
Patent Text Reader

Abstract

To provide a coating film which prevents charging of static electricity, can prevent adsorption of a vortex flow of air, and can prevent reduction of speed.SOLUTION: A coating film 10 formed on a base material 12 contains silicon (Si) and oxygen (O), and is separated into two or more phases, wherein at least the one phase of the phases is a nitrogen containing phase 33 containing nitrogen (N), a residual phase excluding the nitrogen-containing phase of the phases is a non-nitrogen containing phase 34, and a ratio of the nitrogen-containing phase 33 with respect to the total area of the coating film 10 is 20 area% or more and 90 area% or less in the coating film plane.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a coating film, a composite member, a golf club, a fishing rod, a touch panel, a solar cell, a helmet, a rotating body, and a moving body. [Background technology]

[0002] A coating liquid is disclosed that contains 20-60wt% of organic polysilazane, 5-15wt% of alkyl silicate condensate, and 0-80wt% of organic solvent, and the content of methyl groups in the organic polysilazane is 50% or more (see Patent Document 1). In this coating liquid, the organic polysilazane reacts with moisture to form a coating layer of an inorganic-organic composite structure in which an organic functional group is bonded as a side chain to a part of the main chain by siloxane bond, and the alkyl silicate condensate acts as a crosslinking agent to form a crosslinked structure in the coating layer, thereby reducing the elastic modulus of the glass coating film and maintaining flexibility even if the film thickness is more than a certain level. Therefore, the glass coating film can follow the deformation of the article to be coated, the occurrence of cracks and peeling is prevented, and impact resistance and corrosion resistance can be ensured.

[0003] Also disclosed is a golf club in which at least the outer surface of the shaft portion on the club head side of the golf club is coated almost entirely with a coating material having dimples on its surface layer that are made of nano-level minute irregularities. (See Patent Document 2.) With this golf club, air near the club head side of the shaft portion that moves at high speed as the golf club is swung is easily captured by the dimples made of nano-level irregularities in the coating material that coats the outer surface of the shaft portion, and the airflow near the shaft portion generated by the swing maintains its laminar state for a long time, delaying the occurrence of a turbulent state, thereby reducing the air resistance imposed on the golf club. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2021-14514 A [Patent Document 2] JP 2019-51291 A Summary of the Invention [Problem to be solved by the invention]

[0005] Since the glass coating film made from the coating liquid disclosed in Patent Document 1 is insulating, it is easily charged with static electricity due to friction with the air, and air vortexes are attracted to the coating film due to the static electricity adsorption action, and the vortexes act as large air resistance on the glass coating film, causing a decrease in speed. If the coating liquid disclosed in Patent Document 1 is applied to a fishing rod to form a glass coating film on the rod, the rod is easily charged with static electricity due to friction with the air when casting the fishing rod, and air vortexes are attracted to the rod due to the static electricity adsorption action, and the vortexes act as large air resistance on the rod, making it impossible to cast accurately.

[0006] When the coating liquid disclosed in Patent Document 1 is applied to a display touch panel and a glass coating film is formed on the display touch panel, the conductivity of the display touch panel is lost and the touch panel cannot be operated. Also, when the coating liquid disclosed in Patent Document 1 is applied to the front plate of a solar cell panel and a glass coating film is formed on the front plate of the solar cell panel, static electricity easily builds up on the front plate of the solar cell panel, and dust easily adheres to the front plate due to the static electricity adsorption action.

[0007] When the coating liquid disclosed in Patent Document 1 is applied to the surface of a helmet to form a glass coating film on the surface of the helmet, the surface of the helmet is easily charged with static electricity due to friction between the surface of the helmet and the air, and vortexes of air are attracted to the surface of the helmet due to the adsorption of static electricity, increasing air resistance when the helmet is worn. Also, when the coating liquid disclosed in Patent Document 1 is applied to the surface of a rotating body such as a propeller, screw, or blade to form a glass coating film on the surface of the rotating body, the surface of the rotating body is easily charged with static electricity due to friction between the surface of the rotating body and the air, and vortexes of air are attracted to the surface of the rotating body due to the adsorption of static electricity, decreasing the rotation speed of the rotating body.

[0008] When the coating liquid disclosed in Patent Document 1 is applied to a moving body such as an automobile, an airplane, a train, a drone, a rocket, a motorcycle, or a bicycle, and a glass coating film is formed on the moving body, the moving body is easily charged with static electricity due to friction between the moving body and the air, and the air vortex is attracted to the moving body due to the static electricity adsorption action, and the moving speed of the moving body is reduced. Also, when the coating liquid disclosed in Patent Document 1 is applied to the surface of an underwater moving body such as a ship, a submarine, or an underwater drone that comes into contact with water, and a glass coating film is formed on the surface of the underwater moving body that comes into contact with water, the water vortex is attracted to the surface of the underwater moving body that comes into contact with water due to friction between the underwater moving body and the water, and a large water resistance acts, and the underwater moving speed of the underwater moving body is reduced.

[0009] The golf club disclosed in Patent Document 2 is easily charged with static electricity because the coating material covering almost the entire outer surface of the shaft is insulating. Therefore, when this golf club is swung, static electricity is generated in the shaft due to friction with the air, and the static electricity causes vortexes of air to be attracted to the entire outer surface of the shaft. When the vortexes are attracted to the shaft, they create a large air resistance, leading to a decrease in swing speed and causing a decrease in flight distance.

[0010] An object of the present invention is to provide a coating film that is not charged with static electricity, can prevent the adsorption of vortex air currents, and can prevent a decrease in speed. Another object of the present invention is to provide a composite member formed with a coating film that is not charged with static electricity, can prevent the adsorption of vortex air currents, and can prevent a decrease in speed. Another object of the present invention is to provide a golf club formed with a coating film that is not charged with static electricity, can prevent the adsorption of vortex air currents, and can prevent a decrease in swing speed. Another object of the present invention is to provide a fishing rod formed with a coating film that is not charged with static electricity, can prevent the adsorption of vortex air currents, and can perform accurate casting. Another object of the present invention is to provide a touch panel formed with a coating film that allows reliable touch panel operation and prevents the display touch panel from being scratched. Another object of the present invention is to provide a solar cell formed with a coating film that can prevent the adhesion of dust to the solar cell panel and the solar cell panel from being scratched. Another object of the present invention is to provide a helmet formed with a coating film that is not charged with static electricity, can prevent the adsorption of vortex air currents, and can reduce air resistance when worn. Another object of the present invention is to provide a rotating body having a coating film formed thereon that is not charged with static electricity, is capable of preventing the adsorption of vortex air currents, and is capable of preventing a decrease in rotation speed.Another object of the present invention is to provide a moving body having a coating film formed thereon that is not charged with static electricity, is capable of preventing the adsorption of vortex air currents, and is capable of preventing a decrease in movement speed. [Means for solving the problem]

[0011] The present invention, which aims to solve the above-mentioned problems, is based on a coating film formed on a substrate.

[0012] The present invention is characterized in that the coating film contains silicon (Si) and oxygen (O) and is separated into two or more phases, at least one of which is a nitrogen-containing phase that contains nitrogen (N).

[0013] As one example of the present invention, the ratio of the nitrogen-containing phase to the total area of ​​the coating film is 20 area % or more and 90 area % or less on the plane of the coating film.

[0014] In another example of the present invention, the ratio of the nitrogen-containing phase to the total area of ​​the coating film is 30 area % or more and 70 area % or less on the plane of the coating film.

[0015] In another example of the present invention, the nitrogen-containing phase extends in any direction in the coating film and is continuously connected.

[0016] In another example of the present invention, among the phases separated into two or more phases, the remaining phases excluding the nitrogen-containing phase are nitrogen-free phases, and the nitrogen-free phases extend in any direction in the coating film and are separated from each other.

[0017] In another embodiment of the present invention, the electrical resistivity of the nitrogen-containing phase is less than that of the non-nitrogen-containing phase.

[0018] In another example of the present invention, the average thickness of the coating film is 0.2 μm or more and 20 μm or less.

[0019] In another embodiment of the present invention, the electrical resistance of the coating film is smaller than that of the contact surface of the substrate on which the coating film is formed.

[0020] In another example of the present invention, the contact surface of the substrate is any one of a resin, a material containing a resin, glass, and a metal.

[0021] In another example of the present invention, the coating film is either a glass-based inorganic coating film or a glass-based organic / inorganic hybrid coating film.

[0022] Another example of the present invention is a composite material characterized in that a coating film is formed on the contact surface of a substrate.

[0023] In another embodiment of the present invention, the contact surface of the substrate on which the coating film is formed is insulating.

[0024] In another example of the present invention, the contact surface of the substrate on which the coating film is formed is any one of a resin, a material containing a resin, glass, and a metal.

[0025] Another example of the present invention is a golf club having a coating film formed on at least one of the club head and shaft of the golf club.

[0026] Another example of the present invention is a fishing rod having a coating film formed on the rod.

[0027] Another example of the present invention is a touch panel, characterized in that a coating film is formed on a touch panel display.

[0028] Another example of the present invention is a solar cell panel having a coating film formed on a front plate of the solar cell panel.

[0029] Another example of the present invention is a helmet characterized in that a coating film is formed on the surface of the helmet.

[0030] Another example of the present invention is a rotating body characterized in that a coating film is formed on the surface of a propeller, rotor, screw, or blade.

[0031] Another example of the present invention is a moving body in which a coating film is formed on a surface that comes into contact with air, such as an automobile, an airplane, a train, a drone, a rocket, a motorcycle, or a bicycle, or on a surface that comes into contact with water, such as a ship, a submarine, or an underwater drone. Effect of the Invention

[0032] According to the coating film of the present invention, the coating film containing silicon (Si) and oxygen (O) is separated into two or more phases, and at least one of the phases is a nitrogen-containing phase containing nitrogen (N), so that the nitrogen-containing phase has electrical conductivity, and electricity generated in the coating film flows through the nitrogen-containing phase to fall to the ground or discharge. Therefore, the coating film is not charged with static electricity, and no static electricity adsorption occurs, so that adsorption of air vortexes can be prevented, and large air resistance can be prevented from occurring in the coating film. The coating film can prevent adsorption of water vortexes, and large water resistance can be prevented from occurring in the coating film.

[0033] In the coating film, the ratio of the nitrogen-containing phase to the total area of ​​the coating film is 20% by area or more and 90% by area or less on the plane of the coating film, since the ratio of the nitrogen-containing phase to the total area of ​​the coating film is within the above range, the coating film is surely provided with electrical conductivity due to the nitrogen-containing phase, and electricity generated in the coating film flows through the nitrogen-containing phase to fall to the ground or discharge. Therefore, the coating film is not charged with static electricity, and the adsorption of static electricity does not occur, so that the adsorption of air vortexes can be prevented, and the generation of large air resistance in the coating film can be prevented. The coating film can prevent the adsorption of water vortexes, and the generation of large water resistance in the coating film can be prevented.

[0034] In the coating film, the ratio of the nitrogen-containing phase to the total area of ​​the coating film is 30% to 70% by area in the plane of the coating film, and since the ratio of the nitrogen-containing phase to the total area of ​​the coating film is within the above range, the coating film has sufficient conductivity due to the nitrogen-containing phase, and electricity generated in the coating film flows through the nitrogen-containing phase to fall to the ground or discharge. Therefore, the coating film is not charged with static electricity, and no static electricity adsorption occurs, so that the adsorption of air vortexes can be reliably prevented, and the occurrence of large air resistance in the coating film can be prevented. The coating film can reliably prevent the adsorption of water vortexes, and the occurrence of large water resistance in the coating film can be prevented.

[0035] In the coating film in which the nitrogen-containing phase extends in any direction and is connected in series, the conductivity of the coating film is not interrupted by the nitrogen-containing phase being connected in series in the coating film, and electricity generated in the coating film flows through the nitrogen-containing phase and is reliably discharged to the ground or discharged, so that the coating film is not charged with static electricity and no static electricity adsorption occurs, thereby reliably preventing the adsorption of vortexes of air and preventing the generation of large air resistance in the coating film. The coating film reliably prevents the adsorption of vortexes of water and preventing the generation of large water resistance in the coating film.

[0036] In the coating film in which the remaining phases, excluding the nitrogen-containing phase, among the phases separated into two or more phases are nitrogen-free phases, and the nitrogen-free phases extend in any direction in the coating film while being separated from each other, the conductivity of the coating film is not interrupted by the nitrogen-containing phase that connects the separated nitrogen-free phases in series and extends in any direction, and the electricity generated in the coating film flows through the nitrogen-containing phase and is reliably discharged to the ground or discharged, the coating film is not charged with static electricity, and the static electricity adsorption action does not occur, so that the adsorption of vortexes of air can be reliably prevented, and the generation of large air resistance in the coating film can be prevented. The coating film can reliably prevent the adsorption of vortexes of water, and the generation of large water resistance in the coating film can be prevented.

[0037] In the coating film in which the electric resistance of the nitrogen-containing phase is smaller than that of the nitrogen-free phase, the electric resistance of the nitrogen-containing phase is smaller than that of the nitrogen-free phase, so that electricity generated in the coating film flows through the nitrogen-containing phase and is reliably discharged or discharged, the coating film is not charged with static electricity, and the adsorption of static electricity does not occur, so that the adsorption of air vortexes can be reliably prevented, and the generation of large air resistance in the coating film can be prevented. The coating film can reliably prevent the adsorption of water vortexes, and the generation of large water resistance in the coating film can be prevented.

[0038] The coating film having an average thickness of 0.2 μm or more and 20 μm or less has a small mass and can prevent the weight of the object on which the coating film is formed from increasing, and the nitrogen-containing phase of the coating film has electrical conductivity, so that electricity generated in the coating film flows through the nitrogen-containing phase and is reliably discharged or discharged, and the coating film is not charged with static electricity, and no static electricity is adsorbed, so that the adsorption of air vortexes is reliably prevented, and the coating film can prevent the occurrence of large air resistance. The coating film can reliably prevent the adsorption of water vortexes, and can prevent the occurrence of large water resistance.

[0039] The coating film has an electrical resistance smaller than that of the contact surface of the substrate on which the coating film is formed, so that electricity generated in the coating film flows through the nitrogen-containing phase and is reliably discharged or discharged, and the coating film is not charged with static electricity, and no static electricity adsorption occurs, so that the adsorption of air vortexes can be reliably prevented, and the occurrence of large air resistance in the coating film can be prevented. The coating film can reliably prevent the adsorption of water vortexes, and the occurrence of large water resistance in the coating film can be prevented.

[0040] In the coating film, the contact surface of the substrate is any one of resin, resin-containing material, glass, and metal, and the nitrogen-containing phase of the coating film formed on the contact surface of the resin, resin-containing material, and glass has electrical conductivity, so that the contact surface of the resin, resin-containing material, and glass is not charged with static electricity and no static electricity adsorption occurs, so that the adsorption of vortexes of air can be reliably prevented, and the occurrence of large air resistance in the resin, resin-containing material, glass, and metal on which the coating film is formed can be prevented, and the speed reduction of the resin, resin-containing material, glass, and metal in air can be prevented. The coating film can reliably prevent the adsorption of vortexes of water, and the occurrence of large water resistance in the resin, resin-containing material, glass, and metal on which the coating film is formed can be prevented, and the speed reduction of the resin, resin-containing material, glass, and metal in water can be prevented.

[0041] The coating film, which is either a glass-based inorganic coating film or a glass-based organic / inorganic hybrid coating film, is a glass-based inorganic coating film or a glass-based organic / inorganic hybrid coating film that is separated into two or more phases, and at least one of the phases is a nitrogen-containing phase containing nitrogen (N), so that the nitrogen-containing phase has electrical conductivity, and electricity generated in the glass-based inorganic coating film or the glass-based organic / inorganic hybrid coating film flows through the nitrogen-containing phase to fall to the ground or discharge. Therefore, the glass-based inorganic coating film or the glass-based organic / inorganic hybrid coating film is not charged with static electricity, and no static electricity adsorption occurs, so that the adsorption of air vortexes can be reliably prevented, and the generation of large air resistance in the glass-based inorganic coating film or the glass-based organic / inorganic hybrid coating film can be prevented. The coating film can prevent the adsorption of water vortexes, and the generation of large water resistance in the glass-based inorganic coating film or the glass-based organic / inorganic hybrid coating film can be prevented. In addition, since the glass-based inorganic coating film or the glass-based organic / inorganic hybrid coating film has excellent strength, it is possible to prevent the object on which the coating film is formed from being scratched.

[0042] In the composite material having the coating film according to the present invention formed on the contact surface of the substrate, the coating film formed on the contact surface of the composite material is separated into two or more phases, at least one of which is a nitrogen-containing phase containing nitrogen (N), so that the nitrogen-containing phase has electrical conductivity, and electricity generated in the coating film flows through the nitrogen-containing phase to fall to the ground or discharge. Therefore, the composite material having the coating film formed thereon is not charged with static electricity, and no static electricity adsorption occurs, so that adsorption of vortexes of air can be reliably prevented, and large air resistance can be prevented from occurring in the coating film, and the speed reduction of the composite material in air can be prevented. The coating film can reliably prevent adsorption of vortexes of water, and the generation of large water resistance in the coating film can be prevented, and the speed reduction of the composite material in water can be prevented.

[0043] In the composite material according to the present invention, in which the contact surface of the substrate on which the coating film is formed is insulating, the contact surface of the substrate is easily charged with static electricity when the contact surface of the substrate is insulating, but since the coating film formed on the contact surface is separated into two or more phases, at least one of which is a nitrogen-containing phase containing nitrogen (N), the nitrogen-containing phase has electrical conductivity, and electricity generated on the contact surface of the substrate flows through the nitrogen-containing phase to fall to the ground or discharge. Therefore, the composite material on which the coating film is formed is not charged with static electricity, and no static electricity adsorption occurs, so that adsorption of vortexes of air can be reliably prevented, and large air resistance can be prevented from occurring in the coating film, and the speed reduction of the composite material in air can be prevented. The coating film can reliably prevent adsorption of vortexes of water, and the generation of large water resistance in the coating film can be prevented, and the speed reduction of the composite material in water can be prevented.

[0044] In the composite material according to the present invention, the contact surface of the substrate on which the coating film is formed is any one of resin, resin-containing material, glass, and metal, and the nitrogen-containing phase of the coating film formed on the contact surface of the substrate, which is any one of resin, resin-containing material, glass, and metal, is conductive, so that the contact surface of the substrate made of resin, resin-containing material, or glass is not charged with static electricity and no static electricity adsorption occurs, so that the adsorption of vortex currents of air can be reliably prevented, and the generation of large air resistance in the resin, resin-containing material, glass, or metal on which the coating film is formed can be prevented, and the speed reduction in the composite member made of resin, resin-containing material, glass, or metal in air can be prevented. The coating film reliably prevents the adsorption of vortex currents of water, and the generation of large water resistance in the resin, resin-containing material, glass, or metal on which the coating film is formed can be prevented, and the speed reduction in the composite material made of resin, resin-containing material, glass, or metal in water can be prevented.

[0045] In a golf club having the coating film according to the present invention formed on at least one of the club head and shaft, the coating film formed on at least one of the club head and shaft is separated into two or more phases, and at least one of the phases is a nitrogen-containing phase containing nitrogen (N), so that the nitrogen-containing phase has electrical conductivity, and the club head and shaft are not charged with static electricity during the swing of the golf club, and the adsorption of vortex air to the club head and shaft can be reliably prevented, and the swing speed of the golf club can be prevented from decreasing, and the flight distance can be prevented from decreasing. Since the coating film formed on the club head and shaft of the golf club has excellent strength, the coating film can prevent the club head and shaft from being scratched.

[0046] In a fishing rod having a coating film according to the present invention formed on the rod, the coating film formed on the rod is separated into two or more phases, at least one of which is a nitrogen-containing phase containing nitrogen (N), so that the nitrogen-containing phase has electrical conductivity, the rod is not charged with static electricity during casting, and the rod can be reliably prevented from being adsorbed by vortex air currents, allowing for accurate casting. In a fishing rod, the coating film formed on the rod has excellent strength, so that the coating film can prevent the rod from being scratched.

[0047] In a touch panel having the coating film of the present invention formed on a touch panel display, the coating film formed on the touch panel display is separated into two or more phases, and at least one of the phases is a nitrogen-containing phase containing nitrogen (N). Therefore, the nitrogen-containing phase has electrical conductivity, allowing reliable operation of the touch panel, and the coating film can prevent scratches on the touch panel display.

[0048] In a solar cell panel having the coating film of the present invention formed on the front plate of the solar cell panel, the coating film formed on the front plate of the solar cell panel is separated into two or more phases, and at least one of the phases is a nitrogen-containing phase containing nitrogen (N). Therefore, the nitrogen-containing phase has electrical conductivity, the front plate of the solar cell panel is not charged with static electricity, and adhesion of dust to the front plate of the solar cell panel can be prevented, the power generation efficiency of the solar cell panel can be maintained, and the coating film can prevent the solar cell panel from being scratched.

[0049] In the helmet having the coating film according to the present invention formed on its surface, the coating film formed on the surface of the helmet is separated into two or more phases, at least one of which is a nitrogen-containing phase containing nitrogen (N), so that the nitrogen-containing phase has electrical conductivity, the helmet surface is not charged with static electricity, and the adsorption of vortex air on the helmet surface can be prevented, thereby reducing air resistance when the helmet is worn. Since the coating film formed on the helmet surface has excellent strength, the coating film can prevent the helmet from being scratched.

[0050] In the rotating body having the coating film according to the present invention formed on the surface of the propeller, rotor, screw, or blade, the coating film formed on the surface of the propeller, rotor, screw, or blade is separated into two or more phases, and at least one of the phases is a nitrogen-containing phase containing nitrogen (N). Therefore, even if static electricity is generated by friction with the air during the rotation of the rotating body, the surface of the rotating body is not charged with static electricity, and the adsorption of air vortexes can be reliably prevented, and the adsorption of air vortexes to the surface of the rotating body on which the coating film is formed can be prevented, and the generation of large air resistance in the rotating body and the decrease in the rotation speed of the rotating body in air can be prevented. The rotating body can reliably prevent the adsorption of water vortexes, and the generation of large water resistance in the rotating body on which the coating film is formed can be prevented, and the decrease in the speed of the rotating body in water can be prevented. Since the coating film formed on the surface of the rotating body has excellent strength, the coating film can prevent the rotating body from being scratched.

[0051] In the case of a moving body in which the coating film according to the present invention is formed on the surface of an automobile, an aircraft, an electric train, a drone, a rocket, a motorcycle, or a bicycle that comes into contact with air, or the coating film according to the present invention is formed on the surface of a ship, a submarine, or an underwater drone that comes into contact with water, the coating film formed on the surface of the automobile, aircraft, electric train, drone, rocket, motorcycle, or bicycle that comes into contact with air is separated into two or more phases, and at least one of the phases is a nitrogen-containing phase that contains nitrogen (N). Since the nitrogen-containing phase is conductive, and even if static electricity is generated by friction with the air while the moving body is moving, the surface of the moving body will not be charged with static electricity, and it is possible to prevent the adsorption of vortexes of air to the surface of the moving body, which makes it possible to prevent the generation of large air resistance in the moving body and to prevent a decrease in the moving speed of the moving body in the air. The coating film formed on the surface of the moving body that comes into contact with water of a ship, submarine, or underwater drone is separated into two or more phases, at least one of which is a nitrogen-containing phase that contains nitrogen (N), and can reliably prevent adsorption of vortex currents in water, prevent the occurrence of large water resistance in the ship, submarine, or underwater drone on which the coating film is formed, and prevent a decrease in the underwater movement speed of the ship, submarine, or underwater drone in water. The coating film formed on the surface of the moving body has excellent strength, so the coating film can prevent scratches on the moving body. [Brief description of the drawings]

[0052] [Figure 1] An image of a composite material showing an enlarged view of a coating film formed on a substrate. [Diagram 2] 1A to 1C are cross-sectional views for explaining in chronological order the mechanism by which an inorganic coating film or an organic / inorganic hybrid coating film is formed from a coating liquid on the surface of a substrate coated with the coating liquid. [Diagram 3] FIG. 2 is a conceptual diagram showing an example of the structure of an inorganic coating film. [Figure 4] An image showing an example of the structure of an organic / inorganic hybrid coating film. [Diagram 5] FIG. 1 is a perspective view of a golf club shown as an example. [Figure 6] FIG. 13 is a perspective view of a golf club shown as another example. [Figure 7] FIG. 1 is a diagram showing an example of a golf swing using a golf club. [Figure 8] Cross-sectional view taken along line AA in Figure 7. [Figure 9] FIG. 1 is a perspective view of an example fishing rod. [Figure 10] FIG. 1 is a diagram showing an example of casting a fishing rod. [Figure 11] Cross-sectional view of line BB in Figure 10. [Figure 12] FIG. 1 is a perspective view of a touch panel type digital signage display shown as an example. [Figure 13] FIG. 1 is a perspective view of a solar panel shown as an example. [Figure 14] FIG. 14 is an exploded perspective view of the solar panel of FIG. 13. [Figure 15] FIG. 1 is a perspective view of a racing helmet shown as an example. [Figure 16] FIG. 2 is a perspective view of an example propeller. [Figure 17] FIG. 2 is a perspective view of an example screw. [Figure 18] FIG. 1 is a perspective view of an automobile shown as an example. [Figure 19] FIG. 1 is a perspective view of an example aircraft. [Figure 20] FIG. [Figure 21] FIG. 1 is a perspective view of a drone as an example. [Figure 22] FIG. 2 is a perspective view of an example rocket. [Diagram 23] FIG. 1 is a perspective view of a motorcycle as an example. [Figure 24] FIG. 1 is a perspective view of a bicycle as an example. [Diagram 25] A perspective view of an example ship. [Figure 26] FIG. 1 is a perspective view of a submarine as an example. [Figure 27] FIG. 1 is a perspective view of an underwater drone as an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0053] The coating film according to the present invention will be described in detail with reference to the accompanying drawings. FIG. 1 is an image of a composite material 11 showing an enlarged coating film 10 formed on a substrate, and FIG. 2 is a cross-sectional view for explaining in a time series the mechanism by which an inorganic coating film 10a or an organic / inorganic hybrid coating film 10b is formed from a coating liquid on the surface (front and back) of a substrate to which the coating liquid has been applied. FIG. 3 is an image showing an example of the structure of the inorganic coating film 10a, and FIG. 4 is an image showing an example of the structure of the organic / inorganic hybrid coating film 10b. In FIG. 1, the nitrogen-containing phase 33 and the nitrogen-free phase 34 are illustrated as visible images, but in reality, the nitrogen-containing phase 33 and the nitrogen-free phase 34 cannot be visually observed.

[0054] The coating film 10 is formed on a surface 13 (contact surface) of a substrate 12 forming a composite material 11. The coating film 10 is formed on the surface 13 (contact surface) of a club head 16 and a shaft 17 of a golf club 15 (substrate 12) described below, and on the surface 13 (contact surface) of a rod 19 of a fishing rod 18 (substrate 12). It is also formed on the surface 13 (contact surface) of a touch panel display 21 of a touch panel 20 (substrate 12), on the surface 13 (contact surface) of a front plate 23 of a solar cell panel 22 (substrate 12), and on the surface 13 (contact surface) of a helmet 24 (substrate 12).

[0055] Furthermore, it is formed on the surface 13 (contact surface) of the rotor 25 (substrate 12) of the propeller 25a, screw 25b, and blade, and on the surface 13 (contact surface) of the land or air moving body 26 (substrate 12) of the automobile 26a, airplane 26b, train 26c, drone 26d, rocket 26e, motorcycle 26f, and bicycle 26g, and on the surface 13 (contact surface) of the water or underwater moving body 27 (substrate 12) of the ship 27a, submarine 27b, and underwater drone 27c. The coating film 10 is made by coating (applying) the coating liquid 14 to the substrate 12 (golf club 15, fishing rod 18, touch panel 20, solar cell 22, helmet 24, rotor 25, land or air moving body 26, water or underwater moving body 27) to be coated.

[0056] The articles to be coated with the coating liquid 14 (the articles to be formed with the coating film 10) include the club head 16 and shaft 17 of a golf club 15, the rod 19 of a fishing rod 18, the touch panel display 21 of a touch panel 20, the front panel 23 of a solar panel 22, and a helmet 24, as well as land or air vehicles 26 such as a propeller 25a, a screw 25b, a blade rotating body 25, an automobile 26a, an aircraft 26b, a train 26c, a drone 26d, a rocket 26e, a motorcycle 26f, and a bicycle 26g, and surface or underwater vehicles 27 such as a ship 27a, a submarine 27b, and an underwater drone 27c.

[0057] The coating liquid 14 for forming the coating film 10 is coated (applied) on the surface 13 (contact surface) of the substrate 12 (article). The hardened coating liquid 14 forms an inorganic coating film 10a or an organic / inorganic hybrid coating film 10b that covers the surface 13 (contact surface) of the substrate 12 (article). As the raw materials for the coating liquid 14, a liquid organosilicon material (silicon material) consisting of at least one of organic polysilazane (polysilazane) and siloxane, an alkyl silicate condensate, and an inert organic solvent are used. Alternatively, a low molecular weight silane is used. The coating liquid 14 contains a conductive nitrogen-containing liquid agent A and an insulating nitrogen-free liquid agent B dispersed and mixed therein. In the coating liquid 14, the nitrogen-containing liquid A and the nitrogen-free liquid B are incompatible, and the nitrogen-containing liquid A and the nitrogen-free liquid B do not mix at the molecular level, and the phase of the nitrogen-containing liquid A and the phase of the nitrogen-free liquid B are separated to form at least two phases. The ratio of the nitrogen-containing liquid A to the total mass of the liquids A and B, which are the nitrogen-containing liquid A and the nitrogen-free liquid B, is in the range of 40 to 60 wt%, and the ratio of the nitrogen-free liquid B to the total mass is in the range of 40 to 60 wt%. Preferably, the ratio of the nitrogen-containing liquid A is 50 wt% or more (51 to 60 wt%), and the ratio of the nitrogen-free liquid B is less than 50 wt% (40 to 49 wt%).

[0058] Either one of organic polysilazane (perhydropolysilazane (polymeric silane)) and siloxane (polymeric silane) may be used, or a mixture of both may be used. The coating liquid 14 is produced by mixing and stirring an organic silicon material, an alkyl silicate condensate, and an inert organic solvent in a predetermined blending ratio. In the coating liquid 14, the organic silicon material consisting of at least one of organic polysilazane and siloxane, and the alkyl silicate condensate are diluted with an inert organic solvent.

[0059] Organic polysilazane (perhydropolysilazane) is a polymer having Si-N bonds and functional groups (R1 to R3) and formed from -(SiR1R2-NR3)- units represented by the following general formula (1), in which at least one of the functional groups R1 and R2 directly bonded to Si is an organic polymer formed from an organic functional group such as an alkyl group having carbon (C).

[0060] [ka] The organic polysilazane has a content of 50% or more of methyl group (CH3), which is one of the functional groups (R1 to R3) of an organic compound having a structure in which a carbon atom is replaced by three hydrogen atoms. The organic polysilazane may be not only a polymer formed from one type of -(SiR1R2-NR3)- unit, but also a polymer formed from multiple types of -(SiR1R2-NR3)- units having different compositions of functional groups (R1 to R3). Furthermore, the organic polysilazane may be a polymer having a chain, cyclic or crosslinked structure, or a polymer having a combination of these structures.

[0061] As an example of organic polysilazane, organic polysilazane (A) is a -(SiH(CH3)-NH)- unit, -(Si(CH3)2-NH)- unit, -(SiR 1 It is a polymer containing (CH3)-NR3)- units. 1 (CH3)-NR 3 The functional group R1 in the )-unit is H or CH3, and the functional group R3 directly bonded to N is an organic functional group that promotes the reaction. By including organic polysilazane (A) in the coating liquid 14, the reaction after the coating liquid 14 is applied to the surface 13 of the substrate 12 (article) is promoted, and the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b can be formed quickly on the surface 13 of the substrate 12 (article).

[0062] [ka] TIFF2025042239000004.tif56Another example of organic polysilazane is organic polysilazane (B), which is a -(SiH(CH3)-NH)- unit, -(SiR 1 (CH3)-NH)- units, and -(SiR 1 Functional group R of the (CH3)-NH)- unit 1 is an organic functional group that realizes high heat resistance. By including organic polysilazane (B) in the coating liquid 14, it is possible to improve the heat resistance of the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b that covers the surface 13 of the substrate 12 (article).

[0063] [ka] The organic polysilazane contained in the coating liquid 14 may be a mixture of multiple types of organic polysilazanes having different polymer structures. For example, the organic polysilazane may be a mixture of organic polysilazane (A) and organic polysilazane (B). According to a mixing experiment of the organic polysilazane (A) and the organic polysilazane (B), a mixture of 50 mass% of the organic polysilazane (A) and 50 mass% of the organic polysilazane (B) exhibits rust prevention properties equal to or greater than that of the organic polysilazane (A) alone, and has a shorter curing time (time to form the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b) than that of the organic polysilazane (B) alone.

[0064] The organic polysilazane contained in the coating liquid 14 can be one selected from polymethylhydrosilazane, poly-N-methylsilazane, poly-N-(triethylsilyl)allylsilazane, poly-N-(dimethylamino)cyclohexylsilazane, and phenylpolysilazane, or a mixture of two or more of these.

[0065] The siloxane contained in the coating liquid 14 may be any one of a chain siloxane having a chain skeleton and a cyclic siloxane having a cyclic skeleton, or a mixture of two or more of them. Examples of the cyclic siloxane include hexamethylcyclotrisiloxane (CH 18 O3Si4), Octamethylcyclotetrasiloxane (C6H 24 O4Si4), decamethylcyclopentasiloxane (C 10 H 30 O5Si5), or a mixture of two or more of them can be used. The number average molecular weight of the organic polysilazane and siloxane is in the range of 3000 to 150000 g / mol.

[0066] The alkyl silicate condensate is one selected from tetramethyl orthosilicate, tetraethyl orthosilicate, tetra-n-propyl orthosilicate, tetra-i-propyl orthosilicate, tetra-n-butyl orthosilicate, tetra-sec-butyl orthosilicate, methyl polysilicate, and ethyl polysilicate, or a condensate (mixture) of two or more of them. The inert organic solvent is inert to the organic polysilazane and siloxane, and the alkyl silicate condensate, and is selected from dibutyl ether, turpentine oil, benzene, toluene, xylene, and propylene glycol monomethyl ether acetate.

[0067] Since the number average molecular weight of the organic polysilazane and the number average molecular weight of the polysiloxane are within the above ranges, the coating liquid containing the organic polysilazane and / or the polysiloxane can maintain a predetermined viscosity, and an inorganic coating film 10a or an organic / inorganic hybrid coating film 10b can be formed from the coating liquid 14. Since the coating liquid 14 is coated on the surface 13 of the substrate 12 (article) to be coated while maintaining a predetermined viscosity, even if the coating liquid 14 is coated on the surface 13 of the substrate 12 (article) on which minute holes or meshes are formed, the coating liquid 14 does not penetrate into the substrate 12 (article), and an inorganic coating film 10a or an organic / inorganic hybrid coating film 10b having a substantially uniform thickness can be formed on the surface 13 of the substrate 12 (article).

[0068] In the coating liquid 14, the mixing ratio of the organosilicon material (organic polysilazane and / or siloxane) to the total mass of the coating liquid 14 is in the range of 30 to 60 mass%, the mixing ratio of the alkyl silicate condensate to the total mass of the coating liquid 14 is in the range of 10 to 15 mass%, and the mixing ratio of the inert organic solvent to the total mass of the coating liquid 14 is in the range of 30 to 60 mass%. If the mixing ratio of the organosilicon material (organic polysilazane, siloxane) is less than 30 mass%, the content of the organosilicon material is small, and it is not possible to form an inorganic coating film 10a or an organic / inorganic hybrid coating film 10b of a predetermined thickness having excellent flexibility, impact resistance, and corrosion resistance on the surface 13 of the substrate 12 (article). If the mixing ratio of the organosilicon material (organic polysilazane, siloxane) exceeds 60 mass%, the viscosity of the coating liquid 14 increases, and the thickness of the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b becomes larger than necessary. Since the coating liquid 14 has a mixing ratio of the organosilicon material (organic polysilazane, siloxane) in the total mass within the above-mentioned range, it is possible to produce an inorganic coating film 10a or an organic / inorganic hybrid coating film 10b having an appropriate thickness and excellent flexibility, impact resistance, and corrosion resistance.

[0069] If the mixing ratio of the alkyl silicate condensate is less than 10% by mass, the alkyl silicate condensate has a weak effect as a crosslinking agent, and a sufficient crosslinked structure is not formed in the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b. If the mixing ratio of the alkyl silicate condensate exceeds 15% by mass, an unnecessary crosslinked structure is formed in the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b, and the flexibility of the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b becomes greater than necessary. Since the mixing ratio of the alkyl silicate condensate to the total mass of the coating liquid 14 is within the above range, the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b having an appropriate crosslinked structure and appropriate flexibility can be produced by using the coating liquid 14.

[0070] If the blending ratio of the inert organic solvent is less than 30% by mass, the viscosity of the coating liquid 14 becomes high, and the thickness of the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b made therefrom becomes larger than necessary. If the blending ratio of the inert organic solvent exceeds 60% by mass, the viscosity of the coating liquid 14 becomes lower than necessary, and it is not possible to form an inorganic coating film 10a or an organic / inorganic hybrid coating film 10b having a predetermined thickness and excellent flexibility, impact resistance, and corrosion resistance on the surface 13 of the substrate 12 (article). Since the blending ratio of the inert organic solvent to the total mass of the coating liquid 14 is within the above range, it is possible to use the coating liquid 14 to form an inorganic coating film 10a or an organic / inorganic hybrid coating film 10b having an appropriate viscosity and excellent flexibility, impact resistance, and corrosion resistance.

[0071] The coating liquid 14 contains an organosilicon material (organic polysilazane and / or siloxane) in the range of 30 to 60 mass % and an alkyl silicate condensate in the range of 10 to 15 mass % based on the total mass of the coating liquid 14, so that the formation rate of the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b made from the coating liquid 14 can be appropriately controlled. Specifically, the hydrolysis of the alkyl silicate condensate proceeds faster than the condensation of the organic polysilazane and / or siloxane, so that the progress of the condensation reaction of the organic polysilazane and / or siloxane can be delayed by first consuming a part of water (H2O) in the hydrolysis of the alkyl silicate condensate, and the formation rate of the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b can be controlled. In addition, since the hydrolysis of the alkyl silicate condensate occurs first, a crosslinked structure can be reliably formed in the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b to impart flexibility.

[0072] In addition, since the organic solvent is selected from dibutyl ether, turpentine oil, benzene, and toluene, which are inactive against organic polysilazane, siloxane, and alkyl silicate condensates, the condensation reaction of organic polysilazane and / or siloxane does not progress rapidly, and the formation rate of the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b can be appropriately controlled. The coating liquid 14 capable of controlling the formation rate of the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b can easily perform the coating operation on the surface 13 of the substrate 12 (article).

[0073] Low molecular weight silanes are made from chlorosilanes, and contain multiple organic functional groups and hydrolyzable alkoxy groups in one molecule, forming an amorphous glass coating through dehydration crosslinking. Low molecular weight silanes have multifunctional groups that strongly bond with organic substances, and hydrolyzable alkoxy groups that strongly bond with inorganic substances. Low molecular weight silanes can be made into low molecular weight liquids by 100% functionalization (high concentration of vitrification components and solvent-free possible). Furthermore, they do not contain volatile silanol groups, so they have high storage and stability. The hardening speed of low molecular weight silanes can be adjusted, and they can be hand-painted. Low molecular weight silanes can be hand-painted even without solvent (highest concentration of vitrification components) because they are low molecular weight. Furthermore, because they are low molecular weight, they have high wettability and leveling properties, and the glossy aesthetic quality of the finished product is stable.

[0074] The substrate 12 to be coated with the coating liquid 14 (substrate 12 (article) on which the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b is to be formed) may be a plastic molded product (resin), a molded product having a plastic layer as the outermost layer (material containing resin), or a glass molded product (glass). In addition to these molded products, the substrate 12 may be a metal molded product, a rubber molded product, a leather molded product, a wooden molded product, a paper molded product, a woven fabric molded product, a nonwoven fabric molded product, or the like. The shape of these molded products is arbitrary (free). It is preferable that the surface 13 of the substrate 12 (the surface 13 of the substrate 12 in contact with the coating liquid 14) is insulating.

[0075] Materials for plastic molded products include known thermoplastic resins such as polyethylene, polypropylene, polystyrene, polyethylene terephthalate, polybutylene terephthalate, polycarbonate, polyamide (nylon), vinyl chloride resin, acrylic resin, silicone resin, fluororesin, polyimide resin, polysulfone resin, etc., and thermosetting resins such as epoxy resin, melamine resin, phenolic resin, unsaturated polyester resin, etc. Shapes of plastic molded products made of these materials include films, sheets, plates, and various other three-dimensional shapes. Materials for metal molded products include iron, aluminum, duralumin, stainless steel, copper, gold, silver, titanium, nickel, alloys, etc. Shapes of metal molded products made of these materials include plates, rods, and various other three-dimensional shapes.

[0076] The substrates 12 (articles) to be coated with the coating liquid 14 include the club head 16 and shaft 17 of a golf club 15, the rod 19 of a fishing rod 18, the touch panel display 21 of a touch panel 20, the front panel 23 of a solar panel 22, and a helmet 24, as well as propellers 25a, rotors, screws 25b, rotating blades 25, land or air vehicles 26 such as automobiles 26a, aircraft 26b, trains 26c, drones 26d, rockets 26e, motorcycles 26f, and bicycles 26g, and surface or underwater vehicles 27 such as ships 27a, submarines 27b, and underwater drones 27c.

[0077] The coating liquid 14 is coated or sprayed on the surface 13 of the substrate 12 (article) to be coated, and chemically reacts with moisture to form (deposit) a single-layer or multi-layer ultra-thin inorganic coating film 10a or organic / inorganic hybrid coating film 10b. The inorganic coating film 10a or organic / inorganic hybrid coating film 10b is deposited as a coating having an average thickness in the range of 0.2 μm to 20 μm, preferably 0.5 μm to 20 μm.

[0078] There is no particular limitation on the method of coating the surface 13 (contact surface) of the substrate 12 (article) with the coating liquid 14, and the substrate 12 (article) is coated (covered) by a coating method suited to the shape of the substrate 12 (article). For example, the substrate 12 may be coated by a spray method, a dipping method, a brush coating method, a roll coating method, a gravure coating method, a flexography method, an inkjet method, or the like. There is no particular limitation on the amount of the coating liquid 14 to be applied (coated), and the amount of coating is determined according to the surface performance required for the substrate 12 (article) to be coated. Generally, the amount is 0.1 to 20 g / m2 in terms of solid content. 2 The coating amount is 0.1g / m 2 If the coating amount is less than 20 g / m, the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b having the desired properties will not be formed. 2 If it exceeds this value, the thickness of the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b increases more than necessary, and the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b loses its flexibility.

[0079] In addition, as a pretreatment step prior to the coating step of the coating liquid 14, water (H2O) such as purified water may be sprayed onto the surface 13 of the substrate 12 (article) to adhere the water to the surface 13 of the substrate 12. In this way, a chemical reaction between the water adhered to the surface 13 of the substrate 12 (article) and the components contained in the coating liquid 14 is promoted, and an inorganic coating film 10a or an organic / inorganic hybrid coating film 10b can be rapidly formed on the surface 13 of the substrate 12, and a strong inorganic coating film 10a or an organic / inorganic hybrid coating film 10b can be formed on the surface 13 of the substrate 12.

[0080] Furthermore, a coating liquid containing inorganic polysilazane as a main component can be coated as a primer on the surface 13 of the substrate 12 (article) as a pretreatment step prior to the coating step of the coating liquid 14. For example, when a solution of inorganic polysilazane (1 wt % solution) is coated and then the coating liquid is coated, the rust prevention (durability) of the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b is improved compared to when only the coating liquid is simply coated.

[0081] The mechanism by which the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b is formed on the surface 13 of the substrate 12 (article) is as follows. In the formation (film formation) of the inorganic coating film 10a, the surface 13 of the substrate 12 (article) is coated with the coating liquid 14 by a coating process, and then the surface 13 of the substrate 12 is irradiated with infrared rays while being irradiated with ultraviolet rays to heat the surface 13 of the substrate 12 to 400°C or higher. In the formation (film formation) of the organic / inorganic hybrid coating film 10b, the surface 13 of the substrate 12 (article) is coated with the coating liquid 14 by a coating process, and then the surface 13 of the substrate 12 is left at room temperature (normal temperature) without being heated. Alternatively, the surface 13 of the substrate 12 (article) is coated with the coating liquid 14, and then the surface 13 of the substrate 12 is irradiated with ultraviolet rays while being left at room temperature (normal temperature). Alternatively, after coating surface 13 of substrate 12 (article) with coating liquid 14, surface 13 of substrate 12 is irradiated with ultraviolet light and infrared light at the same time to heat surface 14 of substrate 12 to a temperature of less than 400°C.

[0082] As shown in FIG. 2(a), a small amount of moisture (water droplets) is attached to the surface 13 of the substrate 12 (article) due to condensation or humidity in the air (including the case where water (H2O) is sprayed). When the surface 13 of the substrate 12 (article) is coated with a thin film of the coating liquid 14 by a coating process, the -(SiR 1 R 2 -NR 3 )-unit components and / or -(SiR1 R 2 -NR 3 The )-unit component chemically reacts with moisture (H20) in the air, and an inorganic coating film 10a or an organic / inorganic hybrid coating film 10b (glass coating layer (amorphous glass coating)) having an organic composite structure (-(Si(CH3)2-O-Si(CH3)2)-unit in an example of the structural image of the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b shown in Figures 3 and 4) in which an organic functional group is bonded as a side chain to a part of the main chain by a siloxane bond (Si-O-Si) is generated on the surface 13 of the substrate 12. Note that the inorganic coating film 10a is vitrified (inorganized) at approximately 100%. Also, a small amount of gas (NH3, H2) is generated as a by-product of the above chemical reaction. These gases do not remain on the surface of the article but are volatilized (emitted) into the atmosphere.

[0083] As shown in FIG. 2(b), the coating liquid 14 containing organic polysilazane and / or siloxane undergoes a chemical reaction (deammonia cross-linking) with moisture contained in the air in the surface layer 28 in contact with the air, whereby gases such as hydrogen and ammonia, which are by-products of the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b, volatilize from the surface 13 to the outside air, and a coating layer 29 is formed (generated) on the surface side of the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b.

[0084] The coating liquid 14 coated on the surface 13 of the substrate 12 (article) chemically reacts (deammonia cross-linking) with moisture (water droplets) attached to the surface 13 or with hydroxyl groups -OH (see Figures 3 and 4) present as terminal ends on the surface 13 in the back layer 30 in contact with the surface 13 of the substrate 12, causing gases such as hydrogen and ammonia to rise within the coating layer 29 and volatilize from the surface to the outside air, and forming (generating) the coating layer 29 on the back side of the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b.

[0085] First, a coating layer 29 (vitrified (inorganic) or vitrified (inorganic) and organicized portions) is generated in the surface layer 28 and the back layer 30 of the coating liquid 14. Next, the coating layer 29 (vitrified (inorganic) and organicized portions) is formed and expanded from the surface layer 28 side toward the back layer 30 side, and the coating layer 29 (vitrified (inorganic) or vitrified (inorganic) and organicized portions) expands from the back layer 30 side toward the surface layer 28 side, so that the coating layer 30 (vitrified (inorganic) or vitrified (inorganic) and organicized portions) of the intermediate layer 31 is successively formed (generated), and finally, an inorganic coating film 10a or an organic / inorganic hybrid coating film 10b is formed (generated) on the surface layer 28 in contact with the outside air, the back layer 30 in contact with the surface 13 of the substrate 12 (article), and the intermediate layer 31 between the surface layer 28 and the back layer 30.

[0086] The inorganic coating film 10a made of organic polysilazane and / or siloxane is a glass coating layer that is approximately 100%. The inorganic coating film 10a is mainly composed of SiO2 produced by reacting organic polysilazane and / or siloxane, and thus a glass coating layer that spreads easily in a plane and has high density and high hardness (pencil hardness of about 6H to 9H) is formed. The inorganic coating film 10a is formed into a thin film by the coating liquid 14 containing organic polysilazane and / or siloxane.

[0087] The average thickness of the inorganic coating film 10a is in the range of 0.2 μm to 20 μm, preferably 0.5 μm to 20 μm. If the average thickness of the inorganic coating film 10a is less than 0.2 μm, the strength of the inorganic coating film 10a is reduced and the protective function is lost, and the surface 13 of the substrate 12 (article) cannot be sufficiently protected. If the average thickness of the inorganic coating film 10a exceeds 20 μm, the flexibility of the inorganic coating film 10a is reduced, and the inorganic coating film 10a may peel off from the surface 13 due to deformation of the surface 13 of the substrate 12 (article). Although the inorganic coating film 10a is a coating film mainly composed of SiO2, it has excellent flexibility, and together with the anchor effect of the anchor part 32, it will not peel off even if the surface 13 of the substrate 12 (article) is a material that causes deformation such as a cloth material, and the inorganic coating film 10a can maintain the coating state by following the deformation of the surface 13, and can reliably protect the surface 13, thereby preventing the surface 13 from being scratched.

[0088] The organic / inorganic hybrid coating film 10b made of organic polysilazane and / or siloxane is formed of a glass coating layer (amorphous glass coating layer) and an organic coating layer. The organic / inorganic hybrid coating film 10b is mainly composed of SiO2 produced by reacting organic polysilazane and / or siloxane, and thus a coating layer that spreads easily in a plane and has high density and high hardness (vertical hardness of about 6H to 9H) is formed. The low molecular weight silane contained in the coating liquid 14 forms the organic / inorganic hybrid coating film 10b (amorphous glass coating) by dehydration crosslinking. The organic / inorganic hybrid coating film 10b made of low molecular weight silane is formed of a glass coating layer (amorphous glass coating layer) and an organic coating layer.

[0089] The organic / inorganic hybrid coating film 10b is formed into a thin film by the coating liquid 14 containing organic polysilazane and / or siloxane or low molecular weight silane. The average thickness of the organic / inorganic hybrid coating film 10b is in the range of 0.2 μm to 20 μm, preferably in the range of 0.5 μm to 20 μm. If the average thickness of the organic / inorganic hybrid coating film 10b is less than 0.2 μm, the strength of the organic / inorganic hybrid coating film 10b is reduced and the protective function is lost, and the surface 13 of the substrate 12 (article) cannot be sufficiently protected. If the average thickness of the organic / inorganic hybrid coating film 10b exceeds 20 μm, the flexibility of the organic / inorganic hybrid coating film 10b is reduced, and the organic / inorganic hybrid coating film 10b may peel off from the surface 13 due to deformation of the surface 13 of the substrate 12 (article). Although the organic / inorganic hybrid coating film 10b is a coating film whose main component is SiO2, it has excellent flexibility, and coupled with the anchoring effect of the anchor portion 32, it will not peel off even if the surface 13 of the substrate 12 (article) is a cloth material or the like that causes deformation, and can maintain the coating state of the organic / inorganic hybrid coating film 10b by following the deformation of the surface 13.

[0090] As shown in the structural image of the inorganic coating film 10a in Fig. 3 or the structural image of the organic / inorganic hybrid coating film 10b in Fig. 4, a crosslinking reaction occurs between a hydrolysis product having a -(Si(OH)2-O-Si(OH)2)- unit generated by chemically reacting an alkyl silicate condensate with water and a part of the main chain of the siloxane bond (Si-O-Si) in each coating layer (surface layer 28, intermediate layer 31, back layer 30), and a crosslinked structure is formed, so that the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b has a dense and flexible structure. In addition, it is assumed that the formation of a crosslinked structure allows the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b to have a hydrophobic methyl group (CH3) derived from organic polysilazane and / or siloxane and a hydrophilic hydroxyl group (OH) derived from the hydrolysis product of the alkyl silicate condensate to be coordinated on the surface of the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b.

[0091] As shown in FIG. 2(c), the surface 13 of the substrate 12 (article) before being coated with the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b has many micro-level fine irregularities formed due to small scratches generated during the manufacturing process, etc., unless a special surface treatment such as mirror finishing is performed. The coating liquid 14 is coated on the surface 13 of the substrate 12 (article) and hardens while penetrating the inside of the irregularities, so that the anchor parts 32 of the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b that have hardened and penetrated into the inside of the irregularities exert an anchor effect, and the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b adheres more firmly to the surface 13 of the substrate 12 (article). The organic / inorganic hybrid coating film 10b made from low molecular weight silane is a low molecular weight, so it penetrates (permeates) into the entire interior area of ​​the irregularities on the surface 13 of the substrate 12 (article) and hardens throughout the entire interior area of ​​the irregularities, exerting a strong anchor effect.

[0092] When the surface 13 of the substrate 12 (article) is a smooth surface with almost no unevenness, the surface 13 may be roughened to form unevenness with an average roughness of about 1 to 500 μm on the surface 13 as a pretreatment for coating with the coating liquid 14. By performing the roughening treatment in this manner, an anchor effect can be obtained by the anchor portion 32 of the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b. After the roughening treatment, a cleaning treatment is performed in which metal powder, plastic powder, etc. generated on the surface 13 of the substrate 12 (article) is blown away using an air injection means such as an air gun. After the cleaning treatment, condensation, etc. is generated on the surface 13 of the substrate 12 (article) by leaving it for a predetermined time, and naturally occurring moisture is attached to the surface 13.

[0093] In this case, after the surface 13 of the substrate 12 (article) is roughened and cleaned, moisture is actively applied to the surface 13 on which unevenness has been formed by the roughening using a moisture applying means such as a sprayer, and then the coating liquid 14 is coated. In this manner, it is possible to promote a chemical reaction between the moisture applied to the surface 13 of the substrate 12 (article) and the coating liquid 14 in contact with the surface 13. Note that moisture may be applied by a moisture applying means without performing a roughening treatment on the surface 13 of the substrate 12 (article).

[0094] The unevenness initially formed on the surface 13 of the substrate 12 (article) before being coated with the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b made of organic polysilazane and / or siloxane is covered with the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b, so that the surface 13 becomes smoother after coating than before coating.

[0095] The inorganic coating film 10a (coating film) or the organic / inorganic hybrid coating film 10b (coating film) formed on the surface 13 of the substrate 12 (article) is separated into two phases because a conductive nitrogen-containing liquid agent A and an insulating nitrogen-free liquid agent B are mixed into the coating liquid 14 that forms the films 10a and 10b, and the liquid agents A and B are incompatible and the phases are separated into two phases. As shown in the enlarged top view of FIG. 1, the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b is separated into two phases, a nitrogen-containing phase 33 and a nitrogen-free phase 34. The inorganic coating film 10a (coating film) or the organic / inorganic hybrid coating film 10b (coating film) may be separated into three or more phases.

[0096] The nitrogen-containing phase 33 contains silicon (Si) and oxygen (O) as well as nitrogen (N). The nitrogen-free phase 34 contains silicon (Si) and oxygen (O) but does not contain nitrogen (N), and is the remaining phase excluding the nitrogen-containing phase 33. When the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b is separated into three or more phases, at least one of these phases is the nitrogen-containing phase 33.

[0097] In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10), the nitrogen-containing phase 33 extends randomly in any direction (four directions) while being connected in a series, and the nitrogen-containing phase 33 is continuous in the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b. In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10), the nitrogen-free phase 34 extends randomly in any direction (four directions) while being separated from each other, and the non-nitrogen-containing phase 34 is discontinuous in the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b. Note that there are cases where the nitrogen-containing phase 33 is discontinuous and the nitrogen-free phase 34 is discontinuous. There are also cases where the nitrogen-free phase 34 is continuous and the nitrogen-containing phase 33 is discontinuous.

[0098] The electric resistance of the nitrogen-containing phase 33 is smaller than that of the non-nitrogen-containing phase 34. 7 Ω or more 10 11 The electrical resistance of the nitrogen-free phase 34 is in the range of 10 12 Ω or more. The nitrogen-containing phase 33 is a high-resistance conductive phase (antistatic phase), and the nitrogen-free phase 34 is an insulating phase. The electrical resistance of the inorganic coating film 10a (coating film) or the organic / inorganic hybrid coating film 10b (coating film) is smaller than that of the contact surface 13 of the article (substrate 12, golf club 15, fishing rod 18, touch panel 20, solar cell 22, helmet 24, rotating body 25, moving body 26) on which the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b is formed.

[0099] In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10), the continuous nitrogen-containing phase 33 in the coating films 10a and 10b has a predetermined resistance value, but the nitrogen-containing phase 33 is a high-resistance conductive phase (antistatic phase), and the coating films 10a and 10b are not insulators but have electrical conductivity. Therefore, the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b becomes an electrically conductive film having electrical conductivity, and further, the electrical resistance of the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b is smaller than that of the contact surface 13 of the substrate 12 (article) on which the coating films 10a and 10b are formed. Therefore, static electricity generated by friction between the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b and air or water flows through the continuous nitrogen-containing phase 33 and falls to the ground or is discharged, and static electricity does not build up on the coating films 10a and 10b. Even if the nitrogen-containing phase 33 is discontinuous, the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b has an antistatic effect.

[0100] In addition, the electrical resistance of the nitrogen-containing phase 33 is 10 11If it exceeds Ω, the conductivity of the nitrogen-containing phase 33 decreases, the conductivity of the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) is lost, and static electricity generated by friction between the coating films 10a, 10b and air or water cannot flow through the nitrogen-containing phase 33, making it impossible to prevent static electricity from building up on the coating films 10a, 10b. In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10), the electrical resistance of the nitrogen-containing phase 33 is within the above range, so that static electricity reliably flows through the nitrogen-containing phase 33 and falls to the ground or is discharged.

[0101] Furthermore, in the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10), the nitrogen-containing phase 33 extends in any direction in the coating films 10a, 10b while being connected in a series, the nitrogen-free phases 34 extend in any direction in the coating films 10a, 10b while being separated from each other, and the nitrogen-containing phases 33 located between the separated nitrogen-free phases 34 are connected in a series and extend in any direction, so that the conductivity of the coating films 10a, 10b is not interrupted and electricity generated in the coating films 10a, 10b flows through the nitrogen-containing phases 33 to reliably drop to the ground or discharge.

[0102] In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10), the ratio of the nitrogen-containing phase 33 (high resistance conductive phase) to the total area of ​​the coating films 10a, 10b is 20 area% or more and 90 area% or less in the coating film plane, preferably, the ratio of the nitrogen-containing phase 33 to the total area of ​​the coating films 10a, 10b is 30 area% or more and 70 area% or less in the coating film plane. If the ratio of the nitrogen-containing phase 33 to the total area of ​​the coating films 10a, 10b is less than 20 area% in the coating film plane, the ratio of the nitrogen-containing phase 33 (high resistance conductive phase) to the coating films 10a, 10b is low, and the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b cannot exhibit conductivity. If the proportion of the nitrogen-containing phase 33 to the total area of ​​the coating films 10a, 10b exceeds 90 area % in the plane of the coating film, the adhesion of the coating films 10a, 10b to the surface 13 of the substrate 12 (article) is significantly reduced, and a smooth film cannot be formed on the surface 13.

[0103] In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10), the ratio of the nitrogen-containing phase 33 to the total area of ​​the coating films 10a, 10b is within the above-mentioned range, so that the coating films 10a, 10b reliably have conductivity due to the nitrogen-containing phase 33, and the coating films 10a, 10b have high adhesion to the surface 13 of the substrate 12 (article), and can form a smooth film on the surface 13.

[0104] In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10), the coating films 10a, 10b containing silicon (Si) and oxygen (O) are separated into two phases (or two or more phases), one of the phases (at least one of the phases) is a nitrogen-containing phase 33 containing nitrogen (N), and the remaining phase (at least one of the remaining phases) other than the nitrogen-containing phase 33 is a nitrogen-free phase 34, and the electrical resistance of the nitrogen-containing phase 33 is 10 7 Ω or more 1011 Ω or less, and the electrical resistance of the nitrogen-free phase 34 is in the range of 10 12 Since the resistance is Ω or more, the nitrogen-containing phase 33 becomes a high-resistance conductive phase (antistatic phase) having electrical conductivity, and electricity generated in the coating films 10a, 10b flows through the nitrogen-containing phase 33 to fall to the ground or discharge. Therefore, the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) is not charged with static electricity, and no static electricity adsorption occurs, so that adsorption of vortex currents of air or water can be prevented, and the generation of large air resistance or water resistance in the coating films 10a, 10b can be prevented.

[0105] In the composite material 11 having an inorganic coating film 10a (coating film 10) or an organic / inorganic hybrid coating film 10b (coating film 10) formed on the contact surface 13 of a substrate 12 (article), if the contact surface 13 of the substrate 12 is insulating, the contact surface 13 is easily charged with static electricity. However, the coating films 10a, 10b formed on the contact surface 13 of the composite material 11 are separated into two phases (or two or more phases), one of which (or at least one of which) is a nitrogen-containing phase 33 containing nitrogen (N), and the remaining phase (at least one of which) excluding the nitrogen-containing phase 33 is a non-nitrogen-containing phase 34. Therefore, the nitrogen-containing phase 33 has conductivity, and the static electricity generated in the coating films 10a, 10b flows through the nitrogen-containing phase 33 to fall to the ground or be discharged. Therefore, the composite material 11 having the coating films 10a, 10b formed thereon is not charged with static electricity and no static electricity is adsorbed, so that adsorption of vortex currents of air can be reliably prevented, and it is possible to prevent the occurrence of large air resistance in the composite material 11 and to prevent a decrease in the speed of the composite material 11 in the air. The composite material 11 can prevent the adsorption of vortex currents of water, which can prevent the occurrence of large water resistance in the coating films and to prevent a decrease in the speed of the composite material 11 in water.

[0106] Fig. 5 is a perspective view of a golf club 15 shown as an example, and Fig. 6 is a perspective view of a golf club 15 shown as another example. Fig. 7 is a diagram showing an example of a golf swing using the golf club 15, and Fig. 8 is a cross-sectional view taken along line AA in Fig. 7. The golf club 15 shown in Figs. 5 and 6 is a driver, and is formed of a club head 16, a shaft 17 one end of which is connected to the club head 16, and a grip made of a resin material or the like that is fitted to the other end of the shaft 17. The golf club 15 includes fairway woods, utilities, irons (long irons, middle irons, and short irons), and wedges.

[0107] 5 has the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed (covered) on the entire peripheral surface 13 (entire surface area) of the shaft 17. The golf club 15 shown in FIG. 6 has the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed (covered) on the entire peripheral surface 13 (entire surface area) of the shaft 17 and the entire surface 13 (entire surface area) of the club head 16.

[0108] The club head 16 is made of a titanium alloy. There is no particular limit to the material of the club head 16, and the club head 16 may be made of various materials such as titanium alloy, soft iron, stainless steel, full titanium, aluminum alloy, carbon, etc. The shaft 17 is made of a carbon material. There is no particular limit to the material of the shaft 17, and the shaft may be made of steel. The shaft may also be a solid shaft or a hollow shaft.

[0109] The inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire peripheral surface 13 of the shaft 17 of the golf club 15 in FIG. 5 and the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire peripheral surface 13 of the shaft of the golf club 15 in FIG. 6 and the entire surface 13 of the club head 16 are made from the above-mentioned coating liquid 14, which is made of a liquid organosilicon material (silicon material) consisting of at least one of organic polysilazane (polysilazane) and siloxane, an alkyl silicate condensate, and an inert organic solvent, and in which a conductive nitrogen-containing liquid agent A and an insulating nitrogen-free liquid agent B are mixed, or the above-mentioned coating liquid 14, in which a conductive nitrogen-containing liquid agent A and an insulating nitrogen-free liquid agent B are mixed with a low molecular weight silane.

[0110] To form (deposit) the inorganic coating film 10a on the entire circumferential surface 13 of the shaft 17 and the entire surface 13 of the club head 16, the coating liquid 14 is applied to the shaft 17 and the club head 16, and then the circumferential surface 13 of the shaft 17 and the surface 13 of the club head 16 are irradiated with ultraviolet light while irradiating with infrared light to heat the temperature of the circumferential surface 13 of the shaft 17 and the surface 13 of the club head 16 to 400° C. or higher. The inorganic coating film 10a is formed (deposited) on the circumferential surface 13 of the shaft 17 and the surface 13 of the club head 16 with an average thickness in the range of 0.2 μm to 20 μm, preferably 0.5 μm to 20 μm. The golf club 15 on which the thin inorganic coating film 10a mainly composed of SiO2 as described above is formed (deposited) has reduced air resistance, and is highly flexible, impact resistant, water repellent, stain-resistant and rust-resistant. In addition, the inorganic coating film 10a has high film-forming properties and adhesion that make it difficult for it to peel off even when the shaft 17 is twisted or bent.

[0111] To form (deposit) the organic / inorganic hybrid coating film 10b on the entire peripheral surface 13 of the shaft 17 and the entire surface 13 of the club head 16, the coating liquid 14 is applied to the shaft 17 and the club head 16, and then the peripheral surface 13 of the shaft 17 and the surface 13 of the club head 16 are left at room temperature (normal temperature) without being heated. Alternatively, after the coating liquid 14 is applied to the shaft 17 and the club head 16, the peripheral surface 13 of the shaft 17 and the surface 13 of the club head 16 are irradiated with ultraviolet light while being left at room temperature (normal temperature). Alternatively, after the coating liquid 14 is applied to the shaft 17 and the club head 16, the peripheral surface 13 of the shaft 17 and the surface 13 of the club head 16 are irradiated with ultraviolet light while being irradiated with infrared light to heat the temperature of the peripheral surface 13 of the shaft 17 and the surface 13 of the club head 16 to less than 400°C. An organic / inorganic hybrid coating film 10b having an average thickness in the range of 0.2 μm to 20 μm, preferably 0.5 μm to 20 μm, is formed (deposited) on the peripheral surface 13 of the shaft 17 and the surface 13 of the club head 16. The golf club 15 on which the thin organic / inorganic hybrid coating film 10b containing SiO2 as a main component is formed (deposited) has reduced air resistance, and has high flexibility, impact resistance, water repellency, and antifouling and antirust effects, as well as high film formability and adhesion such that the organic / inorganic hybrid coating film 10b is unlikely to peel off even when the shaft 17 is twisted or bent.

[0112] The inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire peripheral surface 13 of the shaft 17 of the golf club 15 and the entire surface 13 of the club head 16 is separated into two phases, a nitrogen-containing phase 33 and a nitrogen-free phase 34, because the conductive nitrogen-containing liquid A and the insulating nitrogen-free liquid B are mixed in the coating liquid 14 that forms the films 10a and 10b, and the liquids A and B are incompatible and the phases are separated into two phases (see FIG. 1). The inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the peripheral surface 13 of the shaft 17 and the surface 13 of the club head 16 may be separated into three or more phases. When the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b is separated into three or more phases, at least one of the phases is the nitrogen-containing phase 33. The nitrogen-containing phase 33 contains silicon (Si) and oxygen (O) as well as nitrogen (N). The nitrogen-free phase 34 contains silicon (Si) and oxygen (O) but does not contain nitrogen (N), and is the remaining phase excluding the nitrogen-containing phase 33.

[0113] In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire peripheral surface 13 of the shaft 17 of the golf club 15 and the entire surface 13 of the club head 16, the nitrogen-containing phase 33 extends randomly in any direction (four directions) and is connected in a series, and the nitrogen-containing phase 33 is continuous in the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b. In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10), the nitrogen-free phase 34 extends randomly in any direction (four directions) and is separated from each other, and the non-nitrogen-containing phase 34 is discontinuous in the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b. Note that there are cases where the nitrogen-containing phase 33 is discontinuous and the non-nitrogen-containing phase 34 is discontinuous. There are also cases where the nitrogen-free phase 34 is continuous and the nitrogen-containing phase 33 is discontinuous.

[0114] The nitrogen-containing phase 33 of the coating films 10a, 10b formed on the entire peripheral surface 13 of the shaft 17 of the golf club 15 and the entire surface 13 of the club head 16 has a smaller electrical resistance than the nitrogen-free phase 34. 7 Ω or more 10 11 The electrical resistance of the nitrogen-free phase 34 is in the range of 10 12 Ω or more. The nitrogen-containing phase 33 is a high-resistance conductive phase (antistatic phase), and the nitrogen-free phase 34 is an insulating phase. The electrical resistance of the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the circumferential surface 13 of the shaft 17 and the surface 13 of the club head 16 is smaller than that of the circumferential surface 13 (contact surface 13) of the shaft 17 and the surface 13 (contact surface 13) of the club head 16 on which the coating films 10a, 10b are formed.

[0115] In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire peripheral surface 13 of the shaft 17 of the golf club 15 and the entire surface 13 of the club head 16, the continuous nitrogen-containing phase 33 in the coating films 10a, 10b has a predetermined resistance value, but the nitrogen-containing phase 33 becomes a high-resistance conductive phase (antistatic phase), so that the coating films 10a, 10b are not insulators and are conductive. Therefore, the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b becomes a conductive film having electrical conductivity, and furthermore, the electrical resistance of the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b is smaller than that of the peripheral surface 13 (contact surface 13) of the shaft 17 and the surface 13 (contact surface 13) of the club head 16 on which the coating films 10a, 10b are formed, so that static electricity generated by friction between the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b and the air flows through the continuous nitrogen-containing phase 33 and falls to the ground or is discharged, and static electricity does not build up on the shaft 17 and the club head 16 (the coating films 10a, 10b) of the golf club 15. Even if the nitrogen-containing phase 33 is discontinuous, the shaft 17 and the club head 16 (the coating films 10a, 10b) have an antistatic effect.

[0116] In addition, the electrical resistance of the nitrogen-containing phase 33 is 10 11If Ω is exceeded, the conductivity of the nitrogen-containing phase 33 decreases, and the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire peripheral surface 13 of the shaft 17 and the entire surface 13 of the club head 16 of the golf club 15 loses conductivity, and static electricity generated by friction between the coating films 10a, 10b and the air cannot flow through the nitrogen-containing phase 33, and it is not possible to prevent static electricity from building up on the shaft 17 and club head 16 of the golf club 15 (the coating films 10a, 10b). The inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire peripheral surface 13 of the shaft 17 of the golf club 15 and on the entire surface 13 of the club head 16 has a nitrogen-containing phase 33 whose electrical resistance is within the above-mentioned range, so that static electricity flows reliably through the nitrogen-containing phase 33 and falls to the ground or is discharged.

[0117] Furthermore, in the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire peripheral surface 13 of the shaft 17 of the golf club 15 and the entire surface 13 of the club head 16, the nitrogen-containing phase 33 extends in any direction in the coating films 10a, 10b while being connected in a series, the nitrogen-free phase 34 extends in any direction in the coating films 10a, 10b while being separated from each other, and the nitrogen-containing phases 33 located between the separated nitrogen-free phases 34 are connected in a series and extend in any direction, so that the conductivity of those coating films 10a, 10b is not interrupted, and static electricity generated in the shaft 17 and club head 17 (those coating films 10a, 10b) of the golf club 15 flows through the nitrogen-containing phase 33 and is reliably dropped to the ground or discharged.

[0118] In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire peripheral surface 13 of the shaft 17 of the golf club 15 and the entire surface 13 of the club head 16, the ratio of the nitrogen-containing phase 33 (high resistance conductive phase) to the total area of ​​the coating films 10a, 10b is 20 area% or more and 90 area% or less in the coating film plane, and preferably, the ratio of the nitrogen-containing phase 33 to the total area of ​​the coating films 10a, 10b is 30 area% or more and 70 area% or less in the coating film plane. If the ratio of the nitrogen-containing phase 33 to the total area of ​​the coating films 10a, 10b is less than 20 area% in the coating film plane, the ratio of the nitrogen-containing phase 33 (high resistance conductive phase) to the coating films 10a, 10b is low, and the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b cannot exhibit sufficient conductivity, and the generated static electricity is charged to the shaft 17 and the club head 16 of the golf club 15. If the proportion of the nitrogen-containing phase 33 to the total area of ​​the coating films 10a, 10b exceeds 90 area % in the coating film plane, the adhesion of the coating films 10a, 10b to the circumferential surface 13 of the shaft 17 and the surface 13 of the club head 16 will be significantly reduced, and a smooth film will not be formed on the circumferential surface 13 of the shaft 17 and the surface 13 of the club head 16.

[0119] The inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire peripheral surface 13 of the shaft 17 of the golf club 15 and the entire surface 13 of the club head 16 has a ratio of the nitrogen-containing phase 33 to the total area of ​​the coating films 10a, 10b within the above-mentioned range, so that the coating films 10a, 10b reliably have sufficient conductivity due to the nitrogen-containing phase 33, and the coating films 10a, 10b have high adhesion to the peripheral surface 13 of the shaft 17 and the surface 13 of the club head 16, and can form a smooth film on the peripheral surface 13 of the shaft 17 and the surface 13 of the club head 16.

[0120] In the golf club 15, an inorganic coating film 10a (coating film 10) or an organic / inorganic hybrid coating film 10b (coating film 10) containing silicon (Si) and oxygen (O) and formed on the entire peripheral surface 13 of a shaft 17 of the golf club 15 and the entire surface 13 of a club head 16 is separated into two phases (or two or more phases), one of the phases (at least one of the phases) is a nitrogen-containing phase 33 containing nitrogen (N), and the remaining phase (at least one of the remaining phases) excluding the nitrogen-containing phase 33 is a nitrogen-free phase 34, and the electrical resistance of the nitrogen-containing phase 33 is 10 7 Ω or more 10 11 Ω or less, and the electrical resistance of the nitrogen-free phase 34 is in the range of 10 12 Since the resistance is Ω or more, the nitrogen-containing phase 33 becomes a high-resistance conductive phase (antistatic phase) having electrical conductivity, and static electricity generated on the circumferential surface 13 of the shaft 17 and the surface 13 of the club head 16 (the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10)) flows through the nitrogen-containing phase 33 to fall to the ground or discharge. Therefore, the circumferential surface 13 of the shaft 17 and the surface 13 of the club head 16 are not charged with static electricity, and no static electricity adsorption occurs, so that adsorption of vortexes of air can be prevented, and large air resistance can be prevented from occurring on the circumferential surface 13 of the shaft 17 and the surface 13 of the club head 16. The golf club 15 can reduce the air resistance on the circumferential surface 13 of the shaft 17 and the surface 13 of the club head 16, and can prevent a decrease in the swing speed of the golf club 15 and a decrease in the flight distance. Since the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the club head 16 or the shaft 17 of the golf club 17 has excellent strength, the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b can prevent the club head 16 or the shaft 17 from being scratched.

[0121] FIG. 9 is a perspective view of a fishing rod 18 as an example, and FIG. 10 is a diagram showing an example of casting the fishing rod 18. FIG. 11 is a cross-sectional view of line BB in FIG. 10. The fishing rod 18 shown in FIG. 9 is a telescopic reel rod, but the fishing rod 18 includes all fishing rods such as a parallel joint type reel rod, a telescopic type Nobe rod, a parallel joint type Nobe rod, and a one-piece rod. The rod types include all rods such as sea bass shore casting rods, egging rods, light saltwater lure rods, offshore rods, bass rods, trout rods, reef and breakwater rods, boat rods, casting rods, and mountain stream rods. The fishing rod 18 shown in FIG. 9 has the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 19) described above formed (covered) on the entire peripheral surface 13 of the rod 19. The fishing rod 18 is made of carbon or glass fiber.

[0122] The inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire peripheral surface 13 of the rod 19 of the fishing rod 18 in FIG. 9 is made from the above-mentioned coating liquid 14, which is made of a liquid organosilicon material (silicon material) consisting of at least one of organic polysilazane (polysilazane) and siloxane, an alkyl silicate condensate, and an inert organic solvent, and in which a conductive nitrogen-containing liquid agent A and an insulating nitrogen-free liquid agent B are mixed, or the above-mentioned coating liquid 14, which is made of a low molecular weight silane, a conductive nitrogen-containing liquid agent A and an insulating nitrogen-free liquid agent B are mixed.

[0123] To form (deposit) the inorganic coating film 10a on the entire peripheral surface 13 of the rod 19 of the fishing rod 18, the coating liquid 14 is applied to the rod 19, and then the peripheral surface 13 of the rod 19 is irradiated with ultraviolet light while irradiating with infrared light to heat the temperature of the peripheral surface 13 of the rod 19 to 400°C or higher. The inorganic coating film 10a having an average thickness in the range of 0.2 μm to 20 μm, preferably 0.5 μm to 20 μm, is formed (deposited) on the peripheral surface 13 of the rod 19. The rod 19 of the fishing rod 18 on which the thin inorganic coating film 10a mainly composed of SiO2 is formed (deposited) has reduced air resistance, high flexibility, impact resistance, water repellency, antifouling and antirust effects, and has high film-forming properties and adhesion such that the inorganic coating film 10a is not easily peeled off even when the rod 19 is twisted or bent.

[0124] To form (form) the organic / inorganic hybrid coating film 10b on the entire peripheral surface 13 of the rod 19 of the fishing rod 18, the coating liquid 14 is applied to the rod 19, and then the peripheral surface 13 of the rod 19 is left at room temperature (normal temperature) without heating. Alternatively, after the coating liquid 14 is applied to the rod 19, the peripheral surface 13 of the rod 19 is irradiated with ultraviolet rays while being left at room temperature (normal temperature). Alternatively, after the coating liquid 14 is applied to the rod 19, the peripheral surface 13 of the rod 19 is irradiated with infrared rays while being irradiated with ultraviolet rays to heat the temperature of the peripheral surface 13 of the rod 19 to less than 400°C. An organic / inorganic hybrid coating film 10b having an average thickness in the range of 0.2 μm to 20 μm, preferably 0.5 μm to 20 μm, is formed (formed) on the peripheral surface 13 of the rod 19. The rod 19 of the fishing rod 18 on which the thin organic / inorganic hybrid coating film 10b mainly composed of SiO2 is formed (deposited) has reduced air resistance and is highly flexible, impact resistant, water repellent, and has anti-fouling and anti-rust effects. In addition, the organic / inorganic hybrid coating film 10b has high film-forming properties and adhesion that make it difficult for it to peel off even when the rod 19 is twisted or bent.

[0125] The inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire peripheral surface 13 of the rod 19 of the fishing rod 18 is separated into two phases, a nitrogen-containing phase 33 and a nitrogen-free phase 34, because the conductive nitrogen-containing liquid agent A and the insulating nitrogen-free liquid agent B are mixed in the coating liquid 14 forming the films 10a and 10b, and the liquid agents A and B are incompatible and the phases are separated into two phases (see FIG. 1). The inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the peripheral surface 13 of the rod 19 may be separated into three or more phases. When the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b is separated into three or more phases, at least one of the phases is the nitrogen-containing phase 33. The nitrogen-containing phase 33 contains silicon (Si) and oxygen (O) as well as nitrogen (N). The nitrogen-free phase 34 contains silicon (Si) and oxygen (O) but does not contain nitrogen (N), and is the remaining phase excluding the nitrogen-containing phase.

[0126] In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire peripheral surface 13 of the rod 19 of the fishing rod 18, the nitrogen-containing phase 33 extends randomly in any direction (four directions) while being connected in a series, and the nitrogen-containing phase 33 is continuous in the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b. In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10), the nitrogen-free phases 34 extend randomly in any direction (four directions) while being separated from each other, and the non-nitrogen-containing phases 34 are discontinuous in the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b. Note that there are cases where the nitrogen-containing phase 33 is discontinuous and the nitrogen-free phase 34 is discontinuous. There are also cases where the nitrogen-free phase 34 is continuous and the nitrogen-containing phase 33 is discontinuous.

[0127] The nitrogen-containing phase 33 of the coating films 10a, 10b formed on the entire peripheral surface 13 of the rod 19 of the fishing rod 18 has a smaller electrical resistance than the nitrogen-free phase 34. 7 Ω or more 10 11 The electrical resistance of the nitrogen-free phase 34 is in the range of 10 12 Ω or more. The nitrogen-containing phase 33 is a high-resistance conductive phase (antistatic phase), and the nitrogen-free phase 34 is an insulating phase. The electrical resistance of the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the peripheral surface 13 of the rod 19 is smaller than that of the peripheral surface 13 (contact surface 13) of the rod 19 on which the coating films 10a, 10b are formed.

[0128] In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire peripheral surface 13 of the rod 19 of the fishing rod 18, the continuous nitrogen-containing phase 33 in the coating films 10a, 10b has a predetermined resistance value, but the nitrogen-containing phase 33 becomes a high-resistance conductive phase (antistatic phase), and the coating films 10a, 10b are not insulators and are conductive. Therefore, the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b becomes a conductive film having electrical conductivity, and furthermore, since the electrical resistance of the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b is smaller than that of the peripheral surface 13 (contact surface 13) of the rod 19 on which the coating films 10a, 10b are formed, static electricity generated by friction between the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b and the air flows through the continuous nitrogen-containing phase 33 and falls to the ground or is discharged, so that static electricity does not build up on the rod 19 (the coating films 10a, 10b) of the fishing rod 18. Even if the nitrogen-containing phase 33 is discontinuous, the rod 19 (the coating films 10a, 10b) has an antistatic effect.

[0129] In addition, the electrical resistance of the nitrogen-containing phase 33 is 10 11If it exceeds Ω, the conductivity of the nitrogen-containing phase 33 decreases, the conductivity of the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the peripheral surface 13 of the rod 19 is lost, and static electricity generated by friction between the coating films 10a, 10b and the air cannot flow through the nitrogen-containing phase 33, and it is not possible to prevent static electricity from being charged to the rod 19 (the coating films 10a, 10b) of the fishing rod 18. In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the peripheral surface 13 of the rod 19 of the fishing rod 18, the electrical resistance of the nitrogen-containing phase 33 is within the above range, so that static electricity reliably flows through the nitrogen-containing phase 33 and falls to the ground or is discharged.

[0130] Furthermore, in the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire peripheral surface 13 of the rod 19 of the fishing rod 18, the nitrogen-containing phase 33 extends in any direction in the coating films 10a, 10b while being connected in a series, the nitrogen-free phase 34 extends in any direction in the coating films 10a, 10b while being separated from one another, and the nitrogen-containing phases 33 located between the separated nitrogen-free phases 34 are connected in a series and extend in any direction, so that the conductivity of those coating films 10a, 10b is not interrupted, and static electricity generated in the rod 19 of the fishing rod 18 (those coating films 10a, 10b) flows through the nitrogen-containing phase 33 and is reliably dropped to the ground or discharged.

[0131] In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire peripheral surface 13 of the rod 19 of the fishing rod 18, the ratio of the nitrogen-containing phase 33 (high resistance conductive phase) to the total area of ​​the coating films 10a, 10b is 20 area% or more and 90 area% or less in the coating film plane, preferably, the ratio of the nitrogen-containing phase 33 to the total area of ​​the coating films 10a, 10b is 30 area% or more and 70 area% or less in the coating film plane. If the ratio of the nitrogen-containing phase 33 to the total area of ​​the coating films 10a, 10b is less than 20 area% in the coating film plane, the ratio of the nitrogen-containing phase 33 (high resistance conductive phase) to the coating films 10a, 10b is low, and the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b cannot exhibit sufficient conductivity, and the generated static electricity is charged to the rod 19 of the fishing rod 18. If the proportion of the nitrogen-containing phase 33 to the total area of ​​the coating films 10a, 10b exceeds 90 area % in the coating film plane, the adhesion of the coating films 10a, 10b to the peripheral surface 13 of the rod 19 of the fishing rod 18 will be significantly reduced, and a smooth film will not be formed on the peripheral surface 13 of the rod 19 of the fishing rod 18.

[0132] In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed over the entire peripheral surface 13 of the rod 19 of the fishing rod 18, the ratio of the nitrogen-containing phase 33 to the total area of ​​the coating films 10a, 10b is within the above-mentioned range, so that the coating films 10a, 10b reliably have sufficient conductivity due to the nitrogen-containing phase 33, and the coating films 10a, 10b have high adhesion to the peripheral surface 13 of the rod 19, and can form a smooth film on the peripheral surface 13 of the rod 19.

[0133] The fishing rod 18 has an inorganic coating film 10a (coating film 10) or an organic / inorganic hybrid coating film 10b (coating film 10) containing silicon (Si) and oxygen (O) separated into two phases (or two or more phases), one of the phases (at least one of the phases) is a nitrogen-containing phase 33 containing nitrogen (N), and the remaining phase (at least one of the remaining phases) excluding the nitrogen-containing phase 33 is a nitrogen-free phase 34, and the electrical resistance of the nitrogen-containing phase 33 is 10 7 Ω or more 10 11 Ω or less, and the electrical resistance of the nitrogen-free phase 34 is in the range of 10 12 Ω or more, the nitrogen-containing phase 33 becomes a high-resistance conductive phase (antistatic phase) having electrical conductivity, and static electricity generated on the circumferential surface 13 of the rod 19 (the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10)) flows through the nitrogen-containing phase 33 to fall to the ground or be discharged. Therefore, the circumferential surface 13 of the rod 19 is not charged with static electricity, and no static electricity adsorption occurs, so that the adsorption of vortex air can be prevented, and the generation of large air resistance on the circumferential surface 13 of the rod 19 can be prevented. The fishing rod 18 can reduce the air resistance on the circumferential surface 13 of the rod 19, and the rod 19 is not charged with static electricity during casting of the fishing rod 18, and the adsorption of vortex air to the rod 19 can be reliably prevented, allowing accurate casting. Since the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the fishing rod 18 has excellent strength, the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b can prevent the rod from being scratched.

[0134] Fig. 12 is a perspective view of a touch panel display 21 of a touch panel type digital signage 20 shown as an example. The touch panel display 21 includes all touch panel displays such as touch panel displays of smartphones, touch panel displays of personal computers, touch panel displays of restaurants, etc. It also includes a touch panel display with a touchless function. In the touch panel type digital signage shown in Fig. 12, the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) described above is formed (covered) on the entire surface 13 of the touch panel display 21.

[0135] The inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the touch panel display 21 of the touch panel type digital signage 20 in Figure 12 is made from the above-mentioned coating liquid 14 consisting of a liquid organosilicon material (silicon material) consisting of at least one of organic polysilazane (polysilazane) and siloxane, an alkyl silicate condensate, and an inert organic solvent, and in which a conductive nitrogen-containing liquid A and an insulating nitrogen-free liquid B are mixed, or from the above-mentioned coating liquid 14 in which a low molecular weight silane is mixed with a conductive nitrogen-containing liquid A and an insulating nitrogen-free liquid B.

[0136] To form (deposit) the inorganic coating film 10a on the entire surface 13 of the touch panel display 21 of the touch panel type digital signage 20, the coating liquid 14 is applied to the touch panel display 21, and then the surface 13 of the touch panel display 21 is irradiated with ultraviolet light while irradiating with infrared light to heat the temperature of the surface 13 of the touch panel display 21 to 400°C or higher. The inorganic coating film 10a having an average thickness in the range of 0.2 μm to 20 μm, preferably 0.5 μm to 20 μm, is formed (deposited) on the surface 13 of the touch panel display 21. The touch panel display 21 of the touch panel type digital signage 20 on which the thin inorganic coating film 10a mainly composed of SiO2 described above is formed (deposited) has high flexibility, impact resistance, water repellency, and antifouling and anticorrosive effects, and also has high film formability and adhesion such that the inorganic coating film 10a is not easily peeled off even when the touch panel display 21 is accidentally deformed.

[0137] To form (deposit) the organic / inorganic hybrid coating film 10b on the entire surface 13 of the touch panel display 21 of the touch panel type digital signage 20, the coating liquid 14 is applied to the touch panel display 21, and then the surface 13 of the touch panel display 21 is left at room temperature (normal temperature) without heating. Alternatively, after the coating liquid 14 is applied to the touch panel display 21, while leaving it at room temperature (normal temperature), ultraviolet rays are irradiated onto the surface 13 of the touch panel display 21. Alternatively, after the coating liquid 14 is applied to the touch panel display 21, while ultraviolet rays are irradiated onto the surface 13 of the touch panel display 21, infrared rays are irradiated to heat the temperature of the surface 13 of the touch panel display 21 to less than 400°C. An organic / inorganic hybrid coating film 10b having an average thickness in the range of 0.2 μm to 20 μm, preferably 0.5 μm to 20 μm, is formed (deposited) on the surface 13 of the touch panel display 21. The touch panel display 21 of the touch panel type digital signage 20 on which the thin organic / inorganic hybrid coating film 10b mainly composed of SiO2 as described above is formed (deposited) has high flexibility, impact resistance, water repellency, and anti-fouling and anti-rust effects, and also has high film forming properties and adhesion that make the organic / inorganic hybrid coating film 10b less likely to peel off even if the touch panel display 21 is inadvertently deformed.

[0138] The inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the touch panel display 21 of the touch panel type digital signage 20 is separated into two phases, a nitrogen-containing phase 33 and a nitrogen-free phase 34, because the conductive nitrogen-containing liquid agent A and the insulating nitrogen-free liquid agent B are mixed in the coating liquid 14 forming the films 10a and 10b, and the liquid agents A and B are incompatible and the phases are separated into two phases (see FIG. 1). The inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the surface 13 of the touch panel display 21 may be separated into three or more phases. When the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b is separated into three or more phases, at least one of the phases is the nitrogen-containing phase 33. The nitrogen-containing phase 33 contains silicon (Si) and oxygen (O) as well as nitrogen (N). The nitrogen-free phase 34 contains silicon (Si) and oxygen (O) but does not contain nitrogen (N), and is the remaining phase excluding the nitrogen-containing phase 33.

[0139] In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the touch panel display 21 of the touch panel type digital signage 20, the nitrogen-containing phase 33 extends randomly in any direction (four directions) while being connected in a series, and the nitrogen-containing phase 33 is continuous in the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b. In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10), the nitrogen-free phase 34 extends randomly in any direction (four directions) while being separated from each other, and the non-nitrogen-containing phase 34 is discontinuous in the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b. Note that there are cases where the nitrogen-containing phase 33 is discontinuous and the nitrogen-free phase 34 is discontinuous. There are also cases where the nitrogen-free phase 34 is continuous and the nitrogen-containing phase 33 is discontinuous.

[0140] The nitrogen-containing phase 33 of the coating films 10a and 10b formed on the entire surface 13 of the touch panel display 21 of the touch panel type digital signage 20 has a smaller electrical resistance than the nitrogen-free phase 34. 7 Ω or more 10 11 The electrical resistance of the nitrogen-free phase 34 is in the range of 10 12 Ω or more. The nitrogen-containing phase 33 is a high-resistance conductive phase (antistatic phase), and the nitrogen-free phase 34 is an insulating phase. The electrical resistance of the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the surface 13 of the touch panel display 21 is smaller than that of the surface 13 (contact surface 13) of the touch panel display 21 on which the coating films 10a, 10b are formed.

[0141] In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the touch panel display 21 of the touch panel type digital signage 20, the continuous nitrogen-containing phase 33 in the coating films 10a, 10b has a predetermined resistance value, but the nitrogen-containing phase 33 becomes a high-resistance conductive phase (antistatic phase), and the coating films 10a, 10b are not insulators but have conductivity. Therefore, the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b becomes a conductive film having conductivity.

[0142] In addition, the electrical resistance of the nitrogen-containing phase 33 is 10 11When the electrical resistance exceeds Ω, the electrical conductivity of the nitrogen-containing phase 33 decreases, and the electrical conductivity of the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the surface 13 of the touch panel display 21 is lost. In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the surface 13 of the touch panel display 21 of the touch panel type digital signage 20, the electrical resistance of the nitrogen-containing phase 33 is within the above range, so that the coating films 10a, 10b can have electrical conductivity. Note that even if the nitrogen-containing phase 33 is discontinuous, the touch panel display 21 (the coating films 10a, 10b) have electrical conductivity.

[0143] Furthermore, in the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed over the entire surface 13 of the touch panel display 21 of the touch panel type digital signage 20, the nitrogen-containing phases 33 extend in any direction in the coating films 10a, 10b while being connected in a series, the nitrogen-free phases 34 extend in any direction in the coating films 10a, 10b while being separated from each other, and the nitrogen-containing phases 33 located between the separated nitrogen-free phases 34 are connected in a series and extend in any direction, so that the conductivity of the coating films 10a, 10b is not interrupted.

[0144] In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the touch panel display 21 of the touch panel type digital signage 20, the ratio of the nitrogen-containing phase 33 (high resistance conductive phase) to the total area of ​​the coating films 10a, 10b is 20 area% or more and 90 area% or less in the coating film plane, and preferably, the ratio of the nitrogen-containing phase 33 to the total area of ​​the coating films 10a, 10b is 30 area% or more and 70 area% or less in the coating film plane. If the ratio of the nitrogen-containing phase 33 to the total area of ​​the coating films 10a, 10b is less than 20 area% in the coating film plane, the ratio of the nitrogen-containing phase 33 (high resistance conductive phase) to the coating films 10a, 10b is low, and the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b cannot exhibit sufficient conductivity. If the proportion of the nitrogen-containing phase 33 to the total area of ​​those coating films 10a, 10b exceeds 90 area% in the plane of the coating film, the adhesion of those coating films 10a, 10b to the surface 13 of the touch panel display 21 of the touch panel type digital signage 20 will be significantly reduced, and a smooth film will not be able to be formed on the surface 13 of the touch panel display 21.

[0145] The inorganic coating film 10a (coating film 10) or organic / inorganic hybrid coating film 10b (coating film 10) formed over the entire surface 13 of the touch panel display 21 of the touch panel type digital signage 20 has a ratio of the nitrogen-containing phase 33 to the total area of ​​the coating films 10a, 10b within the above-mentioned range, so that the coating films 10a, 10b reliably have sufficient conductivity due to the nitrogen-containing phase 33, and the coating films 10a, 10b have high adhesion to the surface 13 of the touch panel display 21, and can form a smooth film on the surface 13 of the touch panel display 21.

[0146] The touch panel display 21 is configured such that an inorganic coating film 10a (coating film 10) or an organic / inorganic hybrid coating film 10b (coating film 10) containing silicon (Si) and oxygen (O) is separated into two phases (or two or more phases), one of the phases (at least one of the phases) is a nitrogen-containing phase 33 containing nitrogen (N), and the remaining phase (at least one of the remaining phases) excluding the nitrogen-containing phase 33 is a nitrogen-free phase 34, and the electrical resistance of the nitrogen-containing phase 33 is 10 7 Ω or more 10 11 Ω or less, and the electrical resistance of the nitrogen-free phase 34 is in the range of 10 12 Since the resistance is Ω or more, the nitrogen-containing phase 33 becomes a high-resistance conductive phase (antistatic phase) having conductivity. Therefore, the conductivity to the touch panel display 21 is not lost, so that the touch panel display 21 can be reliably operated, and the coating films 10a and 10b can prevent the touch panel display 21 from being scratched.

[0147] FIG. 13 is a perspective view of a solar cell panel 22 shown as an example, and FIG. 14 is an exploded perspective view of the solar cell panel 22 of FIG. 13. The solar cell panel 22 is formed of a solar cell module 35 formed in a rectangular shape long in one direction, and a frame 36 made of aluminum, aluminum alloy, or stainless steel and surrounding the outer periphery of the solar cell module 35. As shown in FIG. 14, the solar cell panel 22 is arranged in the order of a protective plate 37 (front plate 23), a sealant 38, a solar cell 39, a sealant 40, and a back plate 41 from the front side to the back side. In the solar cell panel 22 shown in FIG. 14, the inorganic coating film 10a (coating film 10) or an organic / inorganic hybrid coating film 10b (coating film 10) described above is formed (covered) on the entire surface 13 of the front plate 37 (protective plate 37).

[0148] The inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the protective plate 37 (front panel 23) of the solar cell panel 22 in Figure 13 is made from the above-mentioned coating liquid 14, which consists of a liquid organosilicon material (silicon material) consisting of at least one of organic polysilazane (polysilazane) and siloxane, an alkyl silicate condensate, and an inert organic solvent, and in which a conductive nitrogen-containing liquid agent A and an insulating nitrogen-free liquid agent B are mixed, or the above-mentioned coating liquid 14, which consists of a low molecular weight silane, a conductive nitrogen-containing liquid agent A and an insulating nitrogen-free liquid agent B are mixed.

[0149] To form (deposit) the inorganic coating film 10a on the entire surface 13 of the front plate 37 of the solar cell panel 22, the coating liquid 14 is applied to the front plate 37, and then the surface 13 of the front plate 37 is irradiated with ultraviolet light while irradiating with infrared light to heat the temperature of the surface 13 of the front plate 37 to 400°C or higher. The inorganic coating film 10a having an average thickness in the range of 0.2 μm to 20 μm, preferably 0.5 μm to 20 μm, is formed (deposited) on the surface 13 of the front plate 37 of the solar cell panel 22. The front plate 37 of the solar cell panel 22 on which the thin inorganic coating film 10a mainly composed of SiO2 is formed (deposited) has high flexibility, impact resistance, water repellency, and antifouling and antirust effects, and also has high film formability and adhesion such that the inorganic coating film 10a is not easily peeled off even when the front plate 37 is accidentally deformed.

[0150] To form (deposit) the organic / inorganic hybrid coating film 10b on the entire surface 13 of the front plate 37 of the solar cell panel 22, the coating liquid 14 is applied to the front plate 37, and then the surface 13 of the front plate 37 is left at room temperature (normal temperature) without heating. Alternatively, after the coating liquid 14 is applied to the front plate 37, the surface 13 of the front plate 37 is irradiated with ultraviolet rays while being left at room temperature (normal temperature). Alternatively, after the coating liquid 14 is applied to the front plate 37, the surface 13 of the front plate 37 is irradiated with ultraviolet rays while being irradiated with infrared rays to heat the temperature of the surface 13 of the front plate 37 to less than 400°C. The organic / inorganic hybrid coating film 10b having an average thickness in the range of 0.2 μm to 20 μm, preferably 0.5 μm to 20 μm, is formed (deposited) on the surface 13 of the front plate 37. The front plate 37 of the solar cell panel 22 on which the thin organic / inorganic hybrid coating film 10b mainly composed of SiO2 as described above is formed (deposited) has high flexibility, impact resistance, water repellency, and antifouling and antirust effects, and also has high film-forming properties and adhesion such that the organic / inorganic hybrid coating film 10b is not easily peeled off even if the front plate 37 is inadvertently deformed.

[0151] The inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the front panel 37 of the solar cell panel 22 is separated into two phases, a nitrogen-containing phase 33 and a nitrogen-free phase 34, because the coating liquid 14 forming the films 10a, 10b contains a conductive nitrogen-containing liquid agent A and an insulating nitrogen-free liquid agent B, and the liquid agents A and B are incompatible and separate into two phases (see FIG. 1). The inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the surface 13 of the front panel 37 may be separated into three or more phases. When the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b is separated into three or more phases, at least one of the phases is the nitrogen-containing phase 33. The nitrogen-containing phase 33 contains silicon (Si) and oxygen (O) as well as nitrogen (N). The nitrogen-free phase 34 contains silicon (Si) and oxygen (O) but does not contain nitrogen (N), and is the remaining phase excluding the nitrogen-containing phase 33.

[0152] In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the front panel 37 of the solar cell panel 22, the nitrogen-containing phase 33 extends randomly in any direction (four directions) while being connected in a series, and the nitrogen-containing phase 33 is continuous in the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b. In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10), the nitrogen-free phases 34 extend randomly in any direction (four directions) while being separated from each other, and the non-nitrogen-containing phases 34 are discontinuous in the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b. Note that there are cases where the nitrogen-containing phase 33 is discontinuous and the nitrogen-free phase 34 is discontinuous. There are also cases where the nitrogen-free phase 34 is continuous and the nitrogen-containing phase 33 is discontinuous.

[0153] The nitrogen-containing phase 33 of the coating films 10a and 10b formed on the entire surface 13 of the front plate 37 of the solar cell panel 22 has a smaller electrical resistance than the nitrogen-free phase 34. 7 Ω or more 10 11 The electrical resistance of the nitrogen-free phase 34 is in the range of 10 12 Ω or more. The nitrogen-containing phase 33 is a high-resistance conductive phase (antistatic phase), and the nitrogen-free phase 34 is an insulating phase. The electrical resistance of the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the surface 13 of the front plate 37 is smaller than that of the surface 13 (contact surface 13) of the front plate 37 on which the coating films 10a, 10b are formed.

[0154] In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the front panel 37 of the solar cell panel 22, the continuous nitrogen-containing phase 33 in the coating films 10a, 10b has a predetermined resistance value, but the nitrogen-containing phase 33 becomes a high-resistance conductive phase (antistatic phase), so that the coating films 10a, 10b are not insulators and are conductive. Therefore, the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b becomes a conductive film having electrical conductivity, and further, since the electrical resistance of the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b is smaller than that of the surface 13 (contact surface) of the front panel 37 on which these coating films 10a, 10b are formed, static electricity generated by friction between the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b and the air flows through the continuous nitrogen-containing phase 33 and falls to the ground or is discharged, and static electricity is not charged to the front panel 37 (these coating films 10a, 10b) of the solar cell panel 22.

[0155] In addition, the electrical resistance of the nitrogen-containing phase 33 is 10 11If it exceeds Ω, the conductivity of the nitrogen-containing phase 33 decreases, the conductivity of the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the surface 14 of the front panel 37 is lost, and static electricity generated by friction between the coating films 10a, 10b and the air cannot flow through the nitrogen-containing phase 33, making it impossible to prevent static electricity from being charged to the front panel 37 (the coating films 10a, 10b) of the solar cell panel 22. In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the surface 13 of the front panel 37 of the solar cell panel 22, the electrical resistance of the nitrogen-containing phase 33 is within the above range, so that static electricity reliably flows through the nitrogen-containing phase 33 to fall to the ground or be discharged.

[0156] In addition, in the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the front plate 37 of the solar cell panel 22, the nitrogen-containing phase 33 extends in any direction in the coating films 10a, 10b while being connected in a series, the nitrogen-free phase 34 extends in any direction in the coating films 10a, 10b while being separated from each other, and the nitrogen-containing phase 33 located between the separated nitrogen-free phases 34 is connected in a series and extends in any direction, so that the conductivity of the coating films 10a, 10b is not interrupted, and static electricity generated on the front plate 37 of the solar cell panel 22 (the coating films 10a, 10b) flows through the nitrogen-containing phase 33 to be surely discharged to the ground or discharged. Even if the nitrogen-containing phase 33 is discontinuous, the front plate 37 of the solar cell panel 22 (the coating films 10a, 10b) has an antistatic effect.

[0157] In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the front plate 37 of the solar cell panel 22, the ratio of the nitrogen-containing phase 33 (high resistance conductive phase) to the total area of ​​the coating films 10a, 10b is 20 area% or more and 90 area% or less in the coating film plane, and preferably, the ratio of the nitrogen-containing phase 33 to the total area of ​​the coating films 10a, 10b is 30 area% or more and 70 area% or less in the coating film plane. If the ratio of the nitrogen-containing phase 33 to the total area of ​​the coating films 10a, 10b is less than 20 area% in the coating film plane, the ratio of the nitrogen-containing phase 33 (high resistance conductive phase) to the coating films 10a, 10b is low, and the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b cannot exhibit sufficient conductivity, and the generated static electricity is charged to the front plate 37 of the solar cell panel 22. If the proportion of the nitrogen-containing phase 33 to the total area of ​​those coating films 10a, 10b exceeds 90 area % in the coating film plane, the adhesion of those coating films 10a, 10b to surface 13 of front plate 37 of solar cell panel 22 will be significantly reduced, and a smooth film will not be formed on surface 13 of front plate 37 of solar cell panel 22.

[0158] The inorganic coating film 10a (coating film 10) or organic / inorganic hybrid coating film 10b (coating film 10) formed over the entire surface 13 of the front panel 37 of the solar cell panel 22 has a ratio of the nitrogen-containing phase 33 to the total area of ​​the coating films 10a, 10b within the above-mentioned range, so that the coating films 10a, 10b reliably have sufficient conductivity due to the nitrogen-containing phase 33, and the coating films 10a, 10b have high adhesion to the surface 13 of the front panel 37, and can form a smooth film on the surface 13 of the front panel 37.

[0159] In the solar cell panel 22, an inorganic coating film 10a (coating film 10) or an organic / inorganic hybrid coating film 10b (coating film 10) containing silicon (Si) and oxygen (O) is separated into two phases (or two or more phases), one of the phases (at least one of the phases) is a nitrogen-containing phase 33 containing nitrogen (N), and the remaining phase (at least one of the remaining phases) excluding the nitrogen-containing phase 33 is a nitrogen-free phase 34, and the electrical resistance of the nitrogen-containing phase 33 is 10 7 Ω or more 10 11 Ω or less, and the electrical resistance of the nitrogen-free phase 34 is in the range of 10 12 Since the resistance is Ω or more, the nitrogen-containing phase 33 becomes a high-resistance conductive phase (antistatic phase) having electrical conductivity, and static electricity generated on the surface 13 (inorganic coating film 10a (coating film 10) or organic / inorganic hybrid coating film 10b (coating film 10)) of the front plate 37 flows through the nitrogen-containing phase 33 to fall to the ground or be discharged. Therefore, the front plate 37 of the solar cell panel 22 is not charged with static electricity, and no static electricity adsorption occurs, so that adhesion of dust to the front plate 37 of the solar cell panel 22 can be prevented, the power generation efficiency of the solar cell panel 22 can be maintained, and damage to the front plate 37 (protective plate 37) of the solar cell panel 22 can be prevented.

[0160] FIG. 15 is a perspective view of a racing helmet 24 shown as an example. The racing helmet 24 (helmet) shown in FIG. 15 is formed of a shell 42, a shield 43, a chin strap 44, and ventilation 45. An impact absorbing liner and an interior are installed inside the shell 42 of the racing helmet 24. The racing helmet 24 includes four-wheel racing helmets and two-wheel racing helmets, as well as half-lip, jet type, full-face type, and system type. It also includes a road bike helmet (bicycle helmet). The racing helmet 24 in FIG. 15 is formed (covered) with the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) described above on the entire surface 13 of the helmet 24 (the entire surface 13 of the shell 42, the shield 43, and the chin strap 44).

[0161] The inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 (the entire surface 13 of the shell 42, the shield 43, and the chin strap 44) of the racing helmet 24 in Figure 15 is made from the above-mentioned coating liquid 14, which consists of a liquid organosilicon material (silicon material) consisting of at least one of organic polysilazane (polysilazane) and siloxane, an alkyl silicate condensate, and an inert organic solvent, and in which a conductive nitrogen-containing liquid agent A and an insulating nitrogen-free liquid agent B are mixed, or the above-mentioned coating liquid 14, which consists of a low molecular weight silane, a conductive nitrogen-containing liquid agent A and an insulating nitrogen-free liquid agent B are mixed.

[0162] To form (deposit) the inorganic coating film 10b on the entire surface 13 of the racing helmet 24 (the entire surface 13 of the shell 42, the shield 43, and the chin strap 44), the coating liquid 14 is applied to the racing helmet 24, and then the surface 13 of the racing helmet 24 is irradiated with ultraviolet light and infrared light to heat the temperature of the surface 13 of the racing helmet 24 to 400°C or higher. An inorganic coating film 10a having an average thickness in the range of 0.2 μm to 20 μm, preferably 0.5 μm to 20 μm, is formed (deposited) on the surface 13 of the racing helmet 24. The racing helmet 24 on which the thin inorganic coating film 10a mainly composed of SiO2 described above is formed (deposited) has high flexibility, impact resistance, water repellency, and antifouling and antirust effects, and also has high film-forming properties and adhesion such that the inorganic coating film 10a is not easily peeled off even when the racing helmet 24 is accidentally deformed.

[0163] To form (deposit) the organic / inorganic hybrid coating film 10b on the entire surface 13 of the racing helmet 24 (the entire surface 13 of the shell 42, the shield 43, and the chin strap 44), the coating liquid 14 is applied to the racing helmet 24 (the shell 42, the shield 43, and the chin strap 44), and then the surface 13 of the racing helmet 24 is left at room temperature (normal temperature) without heating. Alternatively, after the coating liquid 14 is applied to the racing helmet 24, the surface 13 of the racing helmet 24 is irradiated with ultraviolet rays while being left at room temperature (normal temperature). Alternatively, after the coating liquid 14 is applied to the racing helmet 24, the surface 13 of the racing helmet 24 is irradiated with ultraviolet rays while being irradiated with infrared rays to heat the temperature of the surface 13 of the racing helmet 24 to less than 400°C. An organic / inorganic hybrid coating film 10b having an average thickness in the range of 0.2 μm to 20 μm, preferably in the range of 0.5 μm to 20 μm, is formed (deposited) on the surface 13 of the racing helmet 24. The racing helmet 24 on which the thin organic / inorganic hybrid coating film 10b mainly composed of SiO2 is formed (deposited) has high flexibility, impact resistance, water repellency, and stain and rust resistance, and also has high film-forming properties and adhesion such that the organic / inorganic hybrid coating film 10b is not easily peeled off even if the racing helmet 24 is inadvertently deformed.

[0164] The inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the racing helmet 24 (the entire surface 13 of the shell 42, the shield 43, and the chin strap 44) is separated into two phases, a nitrogen-containing phase 33 and a nitrogen-free phase 34, because the conductive nitrogen-containing liquid agent A and the insulating nitrogen-free liquid agent B are mixed in the coating liquid 14 that forms the films 10a and 10b, and the liquid agents A and B are incompatible and the phases are separated into two phases (see FIG. 1). The inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the racing helmet 24 may be separated into three or more phases. When the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b is separated into three or more phases, at least one of the phases is the nitrogen-containing phase 33. The nitrogen-containing phase 33 contains silicon (Si) and oxygen (O) as well as nitrogen (N). The nitrogen-free phase 34 contains silicon (Si) and oxygen (O) but does not contain nitrogen (N), and is the remaining phase excluding the nitrogen-containing phase 33.

[0165] In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the racing helmet 24 (the entire surface 13 of the shell 42, the shield 43, and the chin strap 44), the nitrogen-containing phase 33 extends randomly in any direction (four directions) and is connected in a series, and the nitrogen-containing phase 33 is continuous in the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b. In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10), the nitrogen-free phases 34 extend randomly in any direction (four directions) and are separated from each other, and the non-nitrogen-containing phases 34 are discontinuous in the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b. Note that there are cases where the nitrogen-containing phase 33 is discontinuous and the non-nitrogen-containing phase 34 is discontinuous. There are also cases where the nitrogen-free phase 34 is continuous and the nitrogen-containing phase 33 is discontinuous.

[0166] The nitrogen-containing phase 22 of the coating films 10a and 10b formed on the entire surface 13 of the racing helmet 24 (the entire surface 13 of the shell 42, the shield 43, and the chin strap 44) has a smaller electrical resistance than the nitrogen-free phase 24. 7 Ω or more 10 11 The electrical resistance of the nitrogen-free phase 34 is in the range of 10 12 Ω or more. The nitrogen-containing phase 33 is a high-resistance conductive phase (antistatic phase), and the nitrogen-free phase 34 is an insulating phase. The electrical resistance of the inorganic coating film 10a (coating film 19) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the racing helmet 24 is smaller than that of the surface 13 (surfaces 13 of the shell 42, shield 43, and chin strap 44) (contact surfaces 13) of the racing helmet 24 on which the coating films 10a, 10b are formed.

[0167] In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the racing helmet 24 (the entire surface 13 of the shell 42, the shield 43, and the chin strap 44), the continuous nitrogen-containing phase 33 in the coating films 10a, 10b has a predetermined resistance value, but the nitrogen-containing phase 33 becomes a high-resistance conductive phase (antistatic phase), so that the coating films 10a, 10b are not insulators and are conductive. Therefore, the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b becomes a conductive film having electrical conductivity, and furthermore, the electrical resistance of the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b is smaller than that of the surface 13 (surfaces 13 of the shell 42, shield 43, and chinstrap 44) (contact surface 13) of the racing helmet 24 on which these coating films 10a, 10b are formed. Therefore, static electricity generated by friction between the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b and the air flows through the continuous nitrogen-containing phase 33 and falls to the ground or is discharged, and static electricity does not build up on the shell 42, the shield 43, or the chinstrap 44 (these coating films 10a, 10b) of the racing helmet 24.

[0168] In addition, the electrical resistance of the nitrogen-containing phase 33 is 10 11If the resistance exceeds Ω, the electrical conductivity of the nitrogen-containing phase 33 decreases, the electrical conductivity of the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the surface 13 (surface 13 of the shell 42, shield 43, and chin strap 44) of the racing helmet 24 is lost, and static electricity generated by friction between the coating films 10a, 10b and the air cannot flow through the nitrogen-containing phase 33, and the charging of static electricity to the racing helmet 24 (the coating films 10a, 10b) cannot be prevented. In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 (the entire surface 13 of the shell 42, shield 43, and chin strap 44) of the racing helmet 24, the electrical resistance of the nitrogen-containing phase 33 is within the above range, so that static electricity flows reliably through the nitrogen-containing phase 33 and falls to the ground or is discharged.

[0169] In addition, in the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 (the entire surface 13 of the shell 42, the shield 43, and the chin strap 44) of the racing helmet 24, the nitrogen-containing phase 33 extends in any direction in the coating films 10a and 10b while being connected in series, the nitrogen-free phase 34 extends in any direction in the coating films 10a and 10b while being separated from each other, and the nitrogen-containing phase 33 located between the separated nitrogen-free phases 34 is connected in series and extends in any direction, so that the conductivity of the coating films 10a and 10b is not interrupted, and static electricity generated in the racing helmet 24 (the coating films 10a and 10b) flows through the nitrogen-containing phase 33 and is reliably dropped to the ground or discharged. Note that even if the nitrogen-containing phase 33 is discontinuous, the racing helmet 24 (the coating films 10a and 10b) has an antistatic effect.

[0170] In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 (the entire surface 13 of the shell 42, the shield 43, and the chin strap 44) of the racing helmet 24, the ratio of the nitrogen-containing phase 33 (high-resistance conductive phase) to the total area of ​​the coating films 10a and 10b is 20 area% or more and 90 area% or less in the coating film plane, and preferably, the ratio of the nitrogen-containing phase 33 to the total area of ​​the coating films 10a and 10b is 30 area% or more and 70 area% or less in the coating film plane. If the ratio of the nitrogen-containing phase 33 to the total area of ​​the coating films 10a and 10b is less than 20 area% in the coating film plane, the ratio of the nitrogen-containing phase 33 (high-resistance conductive phase) to the coating films 10a and 10b is low, and the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b cannot exhibit sufficient conductivity, and the generated static electricity is charged to the racing helmet 24. If the proportion of the nitrogen-containing phase 33 to the total area of ​​those coating films 10a, 10b exceeds 90 area % in the plane of the coating film, the adhesion of those coating films 10a, 10b to the surface 13 of the racing helmet 24 will be significantly reduced, and a smooth film will not be able to be formed on the surface 13 of the racing helmet 24.

[0171] The inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the racing helmet 24 (the entire surface 13 of the shell 42, the shield 43, and the chinstrap 44) has a ratio of the nitrogen-containing phase 33 to the total area of ​​the coating films 10a, 10b within the above-mentioned range, so that the coating films 10a, 10b reliably have conductivity due to the nitrogen-containing phase 33, and the coating films 10a, 10b have high adhesion to the surface 13 of the racing helmet 24, and can form a smooth film on the surface 13 of the racing helmet 24.

[0172] In the racing helmet 24 (helmet), an inorganic coating film 10a (coating film 10) or an organic / inorganic hybrid coating film 10b (coating film 10) containing silicon (Si) and oxygen (O) is separated into two phases (or two or more phases), one of the phases (at least one of the phases) is a nitrogen-containing phase 33 containing nitrogen (N), and the remaining phase (at least one of the remaining phases) other than the nitrogen-containing phase 33 is a nitrogen-free phase 34, and the electrical resistance of the nitrogen-containing phase 33 is 10 7 Ω or more 10 11 Ω or less, and the electrical resistance of the nitrogen-free phase 34 is in the range of 10 12 Since the resistance is Ω or more, the nitrogen-containing phase 33 becomes a high-resistance conductive phase (antistatic phase) having electrical conductivity, and static electricity generated on the surface 13 (surface 13 of the shell 42, shield 43, and chin strap 44) (inorganic coating film 10a (coating film 10) or organic / inorganic hybrid coating film 10b (coating film 10)) of the racing helmet 24 flows through the nitrogen-containing phase 33 and falls to the ground or is discharged. Therefore, the surface 13 (surface 13 of the shell 42, shield 43, and chin strap 44) of the racing helmet 24 is not charged with static electricity, and no static electricity adsorption occurs, so that adsorption of vortexes of air can be prevented, and the occurrence of large air resistance on the surface 13 of the racing helmet 24 can be prevented, and the air resistance on the surface 13 of the racing helmet 24 can be reduced. Since the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the surface 13 of the racing helmet 24 has excellent strength, the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b can prevent the helmet from being scratched.

[0173] FIG. 16 is a perspective view of a propeller 25a as an example, and FIG. 17 is a perspective view of a screw 25b as an example. The propeller 25a includes all propellers used in propeller airplanes. The screw 25b includes all screws used in ships (including combat ships such as aircraft carriers, battleships, and destroyers) and submarines (including submarines). The propeller 25a (rotating body 25) in FIG. 16 and the screw 25b (rotating body 25) in FIG. 17 are formed (coated) with the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) described above on the entire surface 13. The rotating body 25 includes a rotor and blades not shown. The rotor includes a main rotor and a rear rotor of a helicopter.

[0174] The inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the propeller 25a (rotating body 25) in Figure 16 or the screw 25b (rotating body 25) in Figure 17 is made from the above-mentioned coating liquid 14 consisting of a liquid organosilicon material (silicon material) consisting of at least one of organic polysilazane (polysilazane) and siloxane, an alkyl silicate condensate, and an inert organic solvent, and in which a conductive nitrogen-containing liquid A and an insulating nitrogen-free liquid B are mixed, or from the above-mentioned coating liquid 14 in which a conductive nitrogen-containing liquid A and an insulating nitrogen-free liquid B are mixed with a low molecular weight silane.

[0175] To form (deposit) the inorganic coating film 10a on the entire surface 13 of the propeller 25a and the screw 25b, the coating liquid 14 is applied to the propeller 25a and the screw 25b, and then the entire surface 13 of the propeller 25a and the screw 25b is irradiated with ultraviolet light while irradiating with infrared light to heat the surface 13 of the propeller 25a and the screw 25b to 400° C. or higher. The inorganic coating film 10a is formed (deposited) on the surface 13 of the propeller 25a and the screw 25b with an average thickness in the range of 0.2 μm to 20 μm, preferably 0.5 μm to 20 μm. The propeller 25a and the screw 25b on which the thin inorganic coating film 10a mainly composed of SiO2 as described above is formed (deposited) have high flexibility, impact resistance, water repellency, and antifouling and antirust effects, and also have high film-forming properties and adhesion such that the inorganic coating film 10a is not easily peeled off even due to inadvertent deformation of the propeller 25a and the screw 25b.

[0176] To form (form) the organic / inorganic hybrid coating film 10b on the entire surface 13 of the propeller 25a and the screw 25b, the coating liquid 14 is applied to the propeller 25a and the screw 25b, and then the surface 13 of the propeller 25a and the screw 25b is left at room temperature (normal temperature) without heating. Alternatively, after the coating liquid 14 is applied to the propeller 25a and the screw 25b, the surface 13 of the propeller 25a and the screw 25b is irradiated with ultraviolet light while being left at room temperature (normal temperature). Alternatively, after the coating liquid 14 is applied to the propeller 25a and the screw 25b, the surface 13 of the propeller 25a and the screw 25b is irradiated with ultraviolet light while being irradiated with infrared light to heat the temperature of the surface 13 of the propeller 25a and the screw 25b to less than 400°C. An organic / inorganic hybrid coating film 10b having an average thickness in the range of 0.2 μm to 20 μm, preferably 0.5 μm to 20 μm, is formed (deposited) on the surface 13 of the propeller 25a and the screw 25b. The propeller 25a and the screw 25b on which the thin organic / inorganic hybrid coating film 10b containing SiO2 as a main component is formed (deposited) have high flexibility, impact resistance, water repellency, and antifouling and antirust effects, and also have high film formability and adhesion such that the organic / inorganic hybrid coating film 10b is unlikely to peel off even if the propeller 25a and the screw 25b are inadvertently deformed.

[0177] The inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the propeller 25a and the screw 25b is separated into two phases, a nitrogen-containing phase 33 and a nitrogen-free phase 34, because the coating liquid 14 forming the films 10a and 10b contains a conductive nitrogen-containing liquid agent A and an insulating nitrogen-free liquid agent B, and the liquid agents A and B are incompatible and separate into two phases (see FIG. 1). The inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the propeller 25a and the screw 25b may be separated into three or more phases. When the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b is separated into three or more phases, at least one of the phases is the nitrogen-containing phase 33. The nitrogen-containing phase 33 contains silicon (Si) and oxygen (O) as well as nitrogen (N). The nitrogen-free phase 34 contains silicon (Si) and oxygen (O) but does not contain nitrogen (N), and is the remaining phase excluding the nitrogen-containing phase 33.

[0178] In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the propeller 25a and the screw 25b, the nitrogen-containing phase 33 extends randomly in any direction (four directions) while being connected in a series, and the nitrogen-containing phase 33 is continuous in the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b. In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10), the nitrogen-free phase 34 extends randomly in any direction (four directions) while being separated from each other, and the non-nitrogen-containing phase 34 is discontinuous in the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b. Note that there are cases where the nitrogen-containing phase 33 is discontinuous and the nitrogen-free phase 34 is discontinuous. There are also cases where the nitrogen-free phase 34 is continuous and the nitrogen-containing phase 33 is discontinuous.

[0179] The nitrogen-containing phase 33 of the coating films 10a, 10b formed on the entire surface 13 of the propeller 25a and the screw 25b has a smaller electrical resistance than the nitrogen-free phase 34. 7 Ω or more 10 11 The electrical resistance of the nitrogen-free phase 34 is in the range of 10 12 Ω or more. The nitrogen-containing phase 33 is a high-resistance conductive phase (antistatic phase), and the nitrogen-free phase 34 is an insulating phase. The electrical resistance of the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the propeller 25a and the screw 25b is smaller than that of the surface 13 (contact surface 13) of the propeller 25a and the screw 25b on which the coating films 10a, 10b are formed.

[0180] In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the propeller 25a and the screw 25b, the continuous nitrogen-containing phase 33 in the coating films 10a, 10b has a predetermined resistance value, but the nitrogen-containing phase 33 becomes a high-resistance conductive phase (antistatic phase), and the coating films 10a, 10b are not insulators and are therefore conductive. Therefore, the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b becomes a conductive film having electrical conductivity, and further, the electrical resistance of the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b is smaller than that of the surface 13 (contact surface 13) of the propeller 25a and the screw 25b on which the coating films 10a, 10b are formed. Therefore, static electricity generated by friction between the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b and the air flows through the continuous nitrogen-containing phase 33 and falls to the ground or is discharged, and static electricity does not build up on the propeller 25a and the screw 25b (the coating films 10a, 10b).

[0181] In addition, the electrical resistance of the nitrogen-containing phase 33 is 10 11If the resistance exceeds Ω, the conductivity of the nitrogen-containing phase 33 decreases, the conductivity of the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the surface 13 of the propeller 25a and the screw 25b is lost, and static electricity generated by friction between the coating films 10a, 10b and the air cannot flow through the nitrogen-containing phase 33, and the charging of static electricity to the propeller 25a and the screw 25b (the coating films 10a, 10b) cannot be prevented. In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the propeller 25a and the screw 25b, the electrical resistance of the nitrogen-containing phase 33 is within the above range, so that static electricity flows reliably through the nitrogen-containing phase 33 and falls to the ground or is discharged.

[0182] In addition, in the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the propeller 25a and the screw 25b, the nitrogen-containing phase 33 extends in any direction in the coating films 10a, 10b while being connected in series, the nitrogen-free phase 34 extends in any direction in the coating films 10a, 10b while being separated from each other, and the nitrogen-containing phase 33 located between the separated nitrogen-free phases 34 is connected in series and extends in any direction, so that the conductivity of the coating films 10a, 10b is not interrupted, and static electricity generated in the propeller 25a and the screw 25b (the coating films 10a, 10b) flows through the nitrogen-containing phase 33 and is reliably discharged to the ground or discharged. Note that even if the nitrogen-containing phase 33 is discontinuous, the propeller 25a and the screw 25b (the coating films 10a, 10b) have an antistatic effect.

[0183] In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the propeller 25a and the screw 25b, the ratio of the nitrogen-containing phase 33 (high resistance conductive phase) to the total area of ​​the coating films 10a, 10b is 20 area% or more and 90 area% or less in the coating film plane, preferably, the ratio of the nitrogen-containing phase 33 to the total area of ​​the coating films 10a, 10b is 30 area% or more and 70 area% or less in the coating film plane. If the ratio of the nitrogen-containing phase 33 to the total area of ​​the coating films 10a, 10b is less than 20 area% in the coating film plane, the ratio of the nitrogen-containing phase 33 (high resistance conductive phase) to the coating films 10a, 10b is low, and the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b cannot exhibit sufficient conductivity, and the generated static electricity is charged to the propeller 25a and the screw 25b. If the proportion of the nitrogen-containing phase 33 to the total area of ​​the coating films 10a, 10b exceeds 90 area % in the coating film plane, the adhesion of the coating films 10a, 10b to the surfaces 13 of the propeller 25a and the screw 25b is significantly reduced, and a smooth film cannot be formed on the surfaces 13 of the propeller 25a and the screw 25b.

[0184] The inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the propeller 25a and the screw 25b has a ratio of the nitrogen-containing phase 33 to the total area of ​​the coating films 10a, 10b within the above-mentioned range, so that the coating films 10a, 10b reliably have sufficient conductivity due to the nitrogen-containing phase 33, and the coating films 10a, 10b have high adhesion to the surfaces 13 of the propeller 25a and the screw 25b, and can form smooth films on the surfaces 13 of the propeller 25a and the screw 25b.

[0185] The propeller 25a (rotating body 25) and the screw 25b (rotating body 25) (including the rotor and the blades) have an inorganic coating film 10a (coating film 10) or an organic / inorganic hybrid coating film 10b (coating film 10) containing silicon (Si) and oxygen (O) separated into two phases (or two or more phases), one of the phases (at least one of the phases) is a nitrogen-containing phase 33 containing nitrogen (N), and the remaining phase (at least one of the remaining phases) excluding the nitrogen-containing phase 33 is a nitrogen-free phase 34, and the electrical resistance of the nitrogen-containing phase 33 is 10 7 Ω or more 10 11 Ω or less, and the electrical resistance of the nitrogen-free phase 34 is in the range of 10 12 Since the resistance is Ω or more, the nitrogen-containing phase 33 becomes a high-resistance conductive phase (antistatic phase) having electrical conductivity, and static electricity generated on the surface 13 (inorganic coating film 10a (coating film 10) or organic / inorganic hybrid coating film 10b (coating film 10)) of the propeller 25a and the screw 25b flows through the nitrogen-containing phase and falls to the ground or is discharged. Therefore, the surface 13 of the propeller 25a (rotating body 25) (including the rotor and blades) is not charged with static electricity, and static electricity adsorption does not occur, so that adsorption of air vortexes can be prevented, and large air resistance can be prevented from occurring on the surface 13 of the propeller 25a. Also, adsorption of water vortexes on the screw 25b (rotating body 25) can be prevented, and large water resistance can be prevented from occurring on the surface 13 of the screw 25b. The propeller 25a (rotating body 25) and the screw 25b (rotating body 25) (including the rotor and the blades) can reduce the air resistance or water resistance on the surface 13 of the propeller 25a and the screw 25b, and can improve the propulsive force (speed) of a propeller airplane or a ship using the propeller 25a and the screw 25b. The propeller 25a (rotating body 25) and the screw 25b (rotating body 25) (including the rotor and the blades) can prevent the surface 13 from being scratched by the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the surface 13, since the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b has excellent strength.

[0186] Fig. 18 is a perspective view of an automobile 26a as an example, Fig. 19 is a perspective view of an airplane 26b as an example, Fig. 20 is a perspective view of a train 26c as an example, Fig. 21 is a perspective view of a drone 26d as an example, Fig. 22 is a perspective view of a rocket 26e as an example, Fig. 23 is a perspective view of a motorcycle 26f as an example, Fig. 24 is a perspective view of a bicycle 26g as an example.

[0187] In FIG. 18, a racing car 26a is illustrated as an automobile 26a (land or air vehicle 26), but the automobile 26a includes not only the racing car 26a but also all automobiles (including combat vehicles) currently in use and all automobiles (including combat vehicles) to be developed in the future. In FIG. 19, a passenger plane 26b is illustrated as an aircraft 26b (land or air vehicle 26), but not only the passenger plane 26b but also all aircraft currently in use, such as reciprocating engines and fighter planes, and all aircraft to be developed in the future. In FIG. 20, a Shinkansen 26c is illustrated as an electric train 26c (land or air vehicle 26), but not only the Shinkansen 26c but also all electric trains currently in use and all electric trains to be developed in the future are included in the electric train 26c.

[0188] In FIG. 23, a racing bike 26f (land or air vehicle 26) is illustrated, but the bike 26f includes not only the racing bike 26f but also all bikes currently in use and all bikes to be developed in the future. In FIG. 24, a road bike 26g (land or air vehicle 26) is illustrated, but the car 26g includes not only the road bike 26g but also all bicycles currently in use and all bicycles to be developed in the future. The drone 26d is not limited to the one illustrated, and the drone includes all drones currently in use and all drones to be developed in the future. The rocket 26e is not limited to the one illustrated, and the rocket includes all rockets currently in use and all rockets to be developed in the future.

[0189] The above-mentioned inorganic coating film 10a (coating film 10) or organic / inorganic hybrid coating film 10b (coating film 10) is formed (coated) on the entire surface 13 of the parts that come into contact with air during travel, such as the body, bumper, automobile glass, and tires (excluding the tire contact surface that comes into contact with the road surface) of a racing car 26a (automobile 26a) in Fig. 18. The above-mentioned inorganic coating film 10a (coating film 10) or organic / inorganic hybrid coating film 10b (coating film 10) is formed (coated) on the entire surface 13 of the parts that come into contact with air during takeoff, landing, and flight, such as the body and tires (excluding the tire contact surface that comes into contact with the runway) of an airliner 26b (aircraft 26b) in Fig. 19. The entire surface 13 of the Shinkansen 26c (electric train 26c) in Figure 20 (excluding the contact surfaces of the wheels that come into contact with the tracks) that comes into contact with the air while the train is running is formed (covered) with the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) described above.

[0190] The entire surface 13 of the drone 26d in FIG. 21 that comes into contact with the air during flight is formed (coated) with the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10). The entire surface 13 of the rocket 26e in FIG. 22 that comes into contact with the air during flight is formed (coated) with the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10). The entire surface 13 of the body, tires (excluding the contact surface of the tire that comes into contact with the road surface), etc. of the racing bike 26f (bike 26f) in FIG. 23 that comes into contact with the air during travel is formed (coated) with the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10). The entire surfaces 13 of the parts of the road bike 26g (bicycle 26g) in Figure 24 that come into contact with air while riding, such as the frame, handlebars, cranks, pedals, chainwheel, saddle, tires (excluding the contact surface of the tire that comes into contact with the road surface), are formed (covered) with the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) described above.

[0191] Hereinafter, the racing car 26a (automobile 26a) in FIG. 18, the passenger plane 26b (aircraft 26b) in FIG. 19, the Shinkansen 26c (train 26c) in FIG. 20, the drone 26d in FIG. 21, the rocket 26e in FIG. 22, the racing bike 26f (bike 26f) in FIG. 23, and the road bike 26g (bicycle 26g) in FIG. 24 will be collectively referred to as land or aerial vehicles 26. The inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the part of the land or airborne vehicle 26 shown in Figures 18 to 24 that comes into contact with the air is made from the already-described coating liquid 14 consisting of a liquid organosilicon material (silicon material) consisting of at least one of organic polysilazane (polysilazane) and siloxane, an alkyl silicate condensate, and an inert organic solvent, and in which a conductive nitrogen-containing liquid agent A and an insulating nitrogen-free liquid agent B are mixed, or the already-described coating liquid 14 in which a conductive nitrogen-containing liquid agent A and an insulating nitrogen-free liquid agent B are mixed with a low molecular weight silane.

[0192] To form (deposit) the inorganic coating film 10a on the entire surface 13 of the land or aerial moving body 26 that comes into contact with air, the coating liquid 14 is applied to the land or aerial moving body 26, and then the surface 13 of the land or aerial moving body 26 is irradiated with ultraviolet light while irradiating with infrared light to heat the temperature of the surface 13 of the land or aerial moving body 26 to 400°C or higher. The inorganic coating film 10a having an average thickness in the range of 0.2 μm to 20 μm, preferably 0.5 μm to 20 μm, is formed (deposited) on the surface 13 of the land or aerial moving body 26. The land or aerial moving body 26 on which the above-mentioned thin inorganic coating film 10a mainly composed of SiO2 is formed (deposited) has high flexibility, impact resistance, water repellency, and antifouling and anticorrosive effects, and also has high film-forming properties and adhesion such that the inorganic coating film 10a is not easily peeled off even when the land or aerial moving body 26 is accidentally deformed.

[0193] To form (deposit) the organic / inorganic hybrid coating film 10b on the entire surface 13 of the part of the land or aerial moving body 26 that comes into contact with air, the coating liquid 14 is applied to the land or aerial moving body 26, and then the surface 13 of the land or aerial moving body 26 is left at room temperature (normal temperature) without being heated. Alternatively, after the coating liquid 14 is applied to the land or aerial moving body 26, ultraviolet rays are irradiated onto the entire surface 13 of the land or aerial moving body 26 while the surface is left at room temperature (normal temperature). Alternatively, after the coating liquid 14 is applied to the land or aerial moving body 26, ultraviolet rays are irradiated onto the entire surface 13 of the land or aerial moving body 26, while infrared rays are irradiated to heat the temperature of the surface 13 of the land or aerial moving body 26 to less than 400°C. An organic / inorganic hybrid coating film 10b having an average thickness in the range of 0.2 μm to 20 μm, preferably 0.5 μm to 20 μm, is formed (deposited) on the surface 13 of the land or aerial moving body 26. The land or aerial moving body 26 on which the thin organic / inorganic hybrid coating film 10b containing SiO2 as a main component is formed (deposited) has high flexibility, impact resistance, water repellency, and antifouling / antirust effects, and also has high film-forming properties and adhesion such that the organic / inorganic hybrid coating film 10b is unlikely to peel off even when the land or aerial moving body 26 is accidentally deformed.

[0194] The inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the part of the land or air moving body 26 that contacts the air is separated into two phases, a nitrogen-containing phase 33 and a nitrogen-free phase 34, because the conductive nitrogen-containing liquid agent A and the insulating nitrogen-free liquid agent B are mixed in the coating liquid 14 that forms the film, and the liquid agents A and B are incompatible and the phases are separated into two phases (see FIG. 1). Note that the inorganic coating 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the part of the land or air moving body 26 that contacts the air may be separated into three or more phases. When the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b is separated into three or more phases, at least one of the phases is the nitrogen-containing phase 33. The nitrogen-containing phase 33 contains silicon (Si) and oxygen (O) as well as nitrogen (N). The nitrogen-free phase 34 contains silicon (Si) and oxygen (O) but does not contain nitrogen (N), and is the remaining phase excluding the nitrogen-containing phase 33.

[0195] In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the part of the land or air moving body 26 that contacts the air, the nitrogen-containing phase 33 extends randomly in any direction (four directions) and is connected in a series, and the nitrogen-containing phase 33 is continuous in the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b. In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10), the nitrogen-free phase 34 extends randomly in any direction (four directions) and is separated from each other, and the non-nitrogen-containing phase 34 is discontinuous in the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b. Note that there are cases where the nitrogen-containing phase 33 is discontinuous and the non-nitrogen-containing phase 34 is discontinuous. There are also cases where the nitrogen-free phase 34 is continuous and the nitrogen-containing phase 33 is discontinuous.

[0196] The nitrogen-containing phase 33 of the coating films 10a, 10b formed on the entire surface 13 of the land or air vehicle 26 in contact with the air has a smaller electrical resistance than the nitrogen-free phase 34. 7 Ω or more 10 11 The electrical resistance of the nitrogen-free phase 34 is in the range of 10 12 Ω or more. The nitrogen-containing phase 33 is a high-resistance conductive phase (antistatic phase), and the nitrogen-free phase 34 is an insulating phase. The electrical resistance of the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the part of the land or aerial moving body 26 that comes into contact with air is smaller than that of the surface 13 (contact surface 13) of the part of the land or aerial moving body 26 on which the coating films 10a, 10b are formed that comes into contact with air.

[0197] In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the part of the land or airborne vehicle 26 that comes into contact with the air, the continuous nitrogen-containing phase 33 in the coating films 10a, 10b has a predetermined resistance value, but the nitrogen-containing phase 33 becomes a high-resistance conductive phase (antistatic phase), so that the coating films 10a, 10b are not insulators and are conductive. Therefore, the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b becomes a conductive film having electrical conductivity, and further, the electrical resistance of the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b is smaller than that of the surface 13 (contact surface 13) of the part of the land or aerial moving body 26 on which the coating films 10a, 10b are formed, which comes into contact with the air, so that static electricity generated by friction between the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b and the air flows through the continuous nitrogen-containing phase 33 and falls to the ground or is discharged, and static electricity does not build up on the land or aerial moving body 26 (the coating films 10a, 10b).

[0198] In addition, the electrical resistance of the nitrogen-containing phase 33 is 10 11If it exceeds Ω, the conductivity of the nitrogen-containing phase 33 decreases, the conductivity of the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the surface 13 of the land or aerial moving body 26 is lost, and static electricity generated by friction between the coating films 10a, 10b and the air cannot flow through the nitrogen-containing phase 33, making it impossible to prevent static electricity from being charged to the land or aerial moving body 26 (the coating films 10a, 10b). In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the land or aerial moving body 25, the electrical resistance of the nitrogen-containing phase 33 is within the above range, so that static electricity flows reliably through the nitrogen-containing phase 33 and falls to the ground or is discharged.

[0199] In addition, in the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the part of the land or air moving body 26 that contacts the air, the nitrogen-containing phase 33 extends in any direction in the coating films 10a, 10b while being connected in a series, the nitrogen-free phase 34 extends in any direction in the coating films 10a, 10b while being separated from each other, and the nitrogen-containing phase 33 located between the separated nitrogen-free phases 34 is connected in a series and extends in any direction, so that the conductivity of the coating films 10a, 10b is not interrupted, and static electricity generated in the land or air moving body 26 (the coating films 10a, 10b) flows through the nitrogen-containing phase 33 and is reliably discharged to the ground or discharged. Note that even if the nitrogen-containing phase 33 is discontinuous, the land or air moving body 26 (the coating films 10a, 10b) has an antistatic effect.

[0200] In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the part of the land or air moving body 26 that contacts the air, the ratio of the nitrogen-containing phase 33 (high-resistance conductive phase) to the total area of ​​the coating films 10a, 10b is 20 area% or more and 90 area% or less in the coating film plane, and preferably, the ratio of the nitrogen-containing phase to the total area of ​​the coating films 10a, 10b is 30 area% or more and 70 area% or less in the coating film plane. If the ratio of the nitrogen-containing phase 33 to the total area of ​​the coating films 10a, 10b is less than 20 area% in the coating film plane, the ratio of the nitrogen-containing phase 33 (high-resistance conductive phase) to the coating films 10a, 10b is low, and the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b cannot exhibit sufficient conductivity, and the generated static electricity is charged to the land or air moving body 26. If the proportion of the nitrogen-containing phase 33 to the total area of ​​the coating films 10a, 10b exceeds 90 area % in the coating film plane, the adhesion of the coating films 10a, 10b to the surface 13 of the land or aerial moving body 26 will be significantly reduced, and a smooth film will not be formed on the surface 13 of the land or aerial moving body 26.

[0201] The inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the portion of the land or aerial moving body 26 that comes into contact with the air has a ratio of the nitrogen-containing phase 33 to the total area of ​​the coating films 10a, 10b within the above-mentioned range, so that the coating films 10a, 10b reliably have sufficient conductivity due to the nitrogen-containing phase 33, and the coating films 10a, 10b have high adhesion to the surface 13 of the land or aerial moving body 26, and can form a smooth film on the surface 13 of the land or aerial moving body 26.

[0202] A land or airborne vehicle 26 (automobile 26a, aircraft 26b, train 26c, drone 26d, rocket 26e, motorcycle 26f, bicycle 26g) has an inorganic coating film 10a (coating film 10) or an organic / inorganic hybrid coating film 10b (coating film 10) containing silicon (Si) and oxygen (O) separated into two phases (or two or more phases), one of the phases (at least one of the phases) is a nitrogen-containing phase 33 containing nitrogen (N), and the remaining phase (at least one of the remaining phases) excluding the nitrogen-containing phase 33 is a nitrogen-free phase 34, and the electrical resistance of the nitrogen-containing phase 33 is 10 7 Ω or more 10 11 Ω or less, and the electrical resistance of the nitrogen-free phase 34 is in the range of 10 12 Since the resistance is Ω or more, the nitrogen-containing phase 33 becomes a high-resistance conductive phase (antistatic phase) having electrical conductivity, and static electricity generated on the surface 13 (the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10)) of the land or air moving body 26 that comes into contact with the air flows through the nitrogen-containing phase 33 and falls to the ground or is discharged. Therefore, the surface 13 of the part of the land or air moving body 26 (the automobile 26a, the airplane 26b, the train 26c, the drone 26d, the rocket 26e, the motorcycle 26f, the bicycle 26g) that comes into contact with the air is not charged with static electricity, and no static electricity adsorption occurs, so that adsorption of the vortex of the air can be prevented, and the generation of large air resistance on the surface 13 of the land or air moving body 26 can be prevented, and the air resistance on the surface 13 of the land or air moving body 26 can be reduced, and a decrease in the moving speed of the land or air moving body 26 in the air can be prevented. Since the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the surface of a land or air vehicle 26 (automobile 26a, aircraft 26b, train 26c, drone 26d, rocket 26e, motorcycle 26f, bicycle 26g) has excellent strength, the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b can prevent the land or air vehicle 26 from being scratched.

[0203] FIG. 25 is a perspective view of a ship 27a as an example, and FIG. 26 is a perspective view of a submarine 27b as an example. FIG. 27 is a perspective view of an underwater drone 27c as an example. In FIG. 25, a high-speed boat 27a is illustrated as the ship 27a (surface vehicle 27), but the ship 27a includes not only the high-speed boat 27a but also all ships currently in use, such as cargo ships, motor boats, and rubber boats, and all ships to be developed in the future. The submarine 27b (underwater vehicle 27) is not limited to the one illustrated, and the submarine includes all submarines currently in use and all submarines to be developed in the future. The underwater drone 27c (underwater vehicle 27) is not limited to the one illustrated, and the underwater drone includes all underwater drones currently in use and all underwater drones to be developed in the future.

[0204] The entire surface 13 in contact with water of the rudder, screw, bulbous bow, ship bottom, etc. of the high-speed ship 27a (ship) in FIG. 25 is formed (coated) with the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10). The entire surface 13 in contact with water of the submarine 27b in FIG. 26 is formed (coated) with the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10). The entire surface 13 in contact with water of the underwater drone 27c in FIG. 27 is formed (coated) with the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10).

[0205] Hereinafter, the high-speed boat 27a (ship 27a) in FIG. 25, the submarine 27b in FIG. 26, and the underwater drone 27c in FIG. 27 are collectively referred to as the surface or underwater moving body 27. The inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the surface or underwater moving body 27 shown in FIG. 25 to FIG. 27 that comes into contact with water is made from the above-mentioned coating liquid 14, which is made of a liquid organosilicon material (silicon material) consisting of at least one of organic polysilazane (polysilazane) and siloxane, an alkyl silicate condensate, and an inert organic solvent, and in which a conductive nitrogen-containing liquid agent A and an insulating nitrogen-free liquid agent B are mixed, or the above-mentioned coating liquid 14, which is made of a low molecular weight silane and a conductive nitrogen-containing liquid agent A and an insulating nitrogen-free liquid agent B are mixed.

[0206] To form (deposit) the inorganic coating film 10a on the entire surface 13 of the surface or underwater moving body 27 that comes into contact with water, the coating liquid 14 is applied to the surface 13 of the surface or underwater moving body 27, and then the surface 13 of the surface or underwater moving body 27 is irradiated with ultraviolet light while irradiating with infrared light to heat the surface 13 of the surface or underwater moving body 27 to a temperature of 400°C or higher. The surface 13 of the surface or underwater moving body 27 is formed (deposited) with an average thickness of 0.2 μm to 20 μm, preferably 0.5 μm to 20 μm. The surface or underwater moving body 27 on which the above-mentioned thin inorganic coating film 10a mainly composed of SiO2 is formed (deposited) has high flexibility, impact resistance, water repellency, and antifouling and anticorrosive effects, and also has high film-forming properties and adhesion such that the inorganic coating film 10a is unlikely to peel off even when the surface or underwater moving body 27 is accidentally deformed.

[0207] To form (form) the organic / inorganic hybrid coating film 10b on the entire surface 13 of the surface- or underwater moving body 27 that comes into contact with water, the coating liquid 14 is applied to the surface- or underwater moving body 27, and then the surface 13 of the surface- or underwater moving body 27 is left at room temperature (normal temperature) without being heated. Alternatively, after the coating liquid 14 is applied to the surface- or underwater moving body 27, ultraviolet rays are irradiated onto the entire surface 13 of the surface- or underwater moving body 27 while the surface is left at room temperature (normal temperature). Alternatively, after the coating liquid 14 is applied to the surface- or underwater moving body 27, ultraviolet rays are irradiated onto the entire surface 13 of the surface- or underwater moving body 27 while infrared rays are irradiated to heat the temperature of the surface 13 of the surface- or underwater moving body 27 to less than 400° C. An organic / inorganic hybrid coating film 10b having an average thickness in the range of 0.2 μm to 20 μm, preferably 0.5 μm to 20 μm, is formed (deposited) on the surface 13 of the water-borne or underwater moving body 27. The water-borne or underwater moving body 27 on which the thin organic / inorganic hybrid coating film 10b containing SiO2 as a main component is formed (deposited) has high flexibility, impact resistance, water repellency, and antifouling and antirust effects, and also has high film-forming properties and adhesion such that the organic / inorganic hybrid coating film 10b is unlikely to peel off even when the water-borne or underwater moving body 27 is accidentally deformed.

[0208] The inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the water-contacting portion of the water-borne or underwater moving body 27 is separated into two phases, a nitrogen-containing phase 33 and a nitrogen-free phase 34, because the conductive nitrogen-containing liquid A and the insulating nitrogen-free liquid B are mixed in the coating liquid 14 forming the films 10a and 10b, and the liquids A and B are incompatible and separate into two phases (see FIG. 1). The inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the water-contacting portion of the water-borne or underwater moving body 27 may be separated into three or more phases. When the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b is separated into three or more phases, at least one of the phases is the nitrogen-containing phase 33. The nitrogen-containing phase 33 contains silicon (Si) and oxygen (O) as well as nitrogen (N). The nitrogen-free phase 34 contains silicon (Si) and oxygen (O) but does not contain nitrogen (N), and is the remaining phase excluding the nitrogen-containing phase 33.

[0209] In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the water-contacting portion of the water-borne or underwater moving body 27, the nitrogen-containing phase 33 extends randomly in any direction (four directions) while being connected in a series, and the nitrogen-containing phase 33 is continuous in the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b. In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10), the nitrogen-free phase 34 extends randomly in any direction (four directions) while being separated from each other, and the non-nitrogen-containing phase 34 is discontinuous in the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b. Note that there are cases where the nitrogen-containing phase 33 is discontinuous and the nitrogen-free phase 34 is discontinuous. There are also cases where the nitrogen-free phase 34 is continuous and the nitrogen-containing phase 33 is discontinuous.

[0210] The nitrogen-containing phase 33 of the coating films 10a, 10b formed on the entire surface 13 of the water-contacting portion of the surface or underwater moving body 27 has a smaller electric resistance than the nitrogen-free phase 34. 7 Ω or more 10 11 The electrical resistance of the nitrogen-free phase 34 is in the range of 10 12 Ω or more. The nitrogen-containing phase 33 is a high-resistance conductive phase (antistatic phase), and the nitrogen-free phase 34 is an insulating phase. The electrical resistance of the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the surface- or submersible moving body 27 that comes into contact with water is smaller than that of the surface 13 (contact surface 13) of the surface- or submersible moving body 27 that comes into contact with water on which the coating films 10a, 10b are formed.

[0211] In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the portion of the surface or underwater moving body 27 that comes into contact with water, the continuous nitrogen-containing phase 33 in the coating films 10a, 10b has a predetermined resistance value, but the nitrogen-containing phase becomes a high-resistance conductive phase (antistatic phase), and the coating films 10a, 10b are not insulators and are conductive. Therefore, the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b becomes a conductive film having electrical conductivity, and further, the electrical resistance of the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b is smaller than that of the surface 13 (contact surface 13) of the surface- or underwater moving body 27 on which the coating films 10a, 10b are formed, which comes into contact with water. Therefore, static electricity generated by friction between the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b and the water flows through the continuous nitrogen-containing phase 33 and sinks to the ground or is discharged, and static electricity does not build up on the surface- or underwater moving body 27 (the coating films 10a, 10b).

[0212] In addition, the electrical resistance of the nitrogen-containing phase 33 is 10 11If the resistance exceeds Ω, the conductivity of the nitrogen-containing phase 33 decreases, the conductivity of the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the surface 13 of the water- or underwater moving body 27 is lost, and static electricity generated by friction between the coating films 10a, 10b and the air cannot flow through the nitrogen-containing phase 33, making it impossible to prevent static electricity from being charged to the water- or underwater moving body 27 (the coating films 10a, 10b). In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the water- or underwater moving body 27, the electrical resistance of the nitrogen-containing phase 33 is within the above range, so that static electricity flows reliably through the nitrogen-containing phase 33 and falls to the ground or is discharged.

[0213] In addition, the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the water-contacting portion of the on-water or underwater moving body 27 has a nitrogen-containing phase 33 that extends in any direction in the coating films 10a, 10b and is connected in series, the nitrogen-free phase 34 extends in any direction in the coating films 10a, 10b and is separated from each other, and the nitrogen-containing phase 33 located between the separated nitrogen-free phases 34 is connected in series and extends in any direction, so that the conductivity of the coating films 10a, 10b is not interrupted, and static electricity generated on the on-water or underwater moving body 27 (the coating films 10a, 10b) flows through the nitrogen-containing phase 33 and is reliably discharged to the ground or discharged. Even if the nitrogen-containing phase 33 is discontinuous, the on-water or underwater moving body 27 (the coating films 10a, 10b) has an antistatic effect.

[0214] In the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the water-contacting portion of the on-water or underwater moving body 27, the ratio of the nitrogen-containing phase 33 (high-resistance conductive phase) to the total area of ​​the coating films 10a, 10b is 20% to 90% by area in the plane of the coating film, preferably, the ratio of the nitrogen-containing phase to the total area of ​​the coating films 10a, 10b is 30% to 70% by area in the plane of the coating film. If the ratio of the nitrogen-containing phase 33 to the total area of ​​the coating films 10a, 10b is less than 20% by area in the plane of the coating film, the ratio of the nitrogen-containing phase 33 (high-resistance conductive phase) to the coating films 10a, 10b is low, and the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b cannot exhibit sufficient conductivity, and the generated static electricity is charged to the on-water or underwater moving body 27. If the proportion of the nitrogen-containing phase 33 to the total area of ​​the coating films 10a, 10b exceeds 90 area % in the coating film plane, the adhesion of the coating films 10a, 10b to the surface 14 of the water-borne or underwater moving body 27 will be significantly reduced, and a smooth film will not be formed on the surface 13 of the water-borne or underwater moving body 27.

[0215] The inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the entire surface 13 of the portion of the surface- or underwater moving body 27 that comes into contact with water has a ratio of the nitrogen-containing phase 33 to the total area of ​​the coating films 10a, 10b within the above-mentioned range, so that the coating films 10a, 10b reliably have sufficient conductivity due to the nitrogen-containing phase 33, and the coating films 10a, 10b have high adhesion to the surface 13 of the surface- or underwater moving body 27, and can form a smooth film on the surface 13 of the surface- or underwater moving body 27.

[0216] In a surface or underwater moving body 27 (a ship 27a, a submarine 27b, an underwater drone 27c), an inorganic coating film 10a (coating film 10) or an organic / inorganic hybrid coating film 10b (coating film 10) containing silicon (Si) and oxygen (O) is separated into two phases (or two or more phases), one of the phases (at least one of the phases) is a nitrogen-containing phase 33 containing nitrogen (N), and the remaining phase (at least one of the remaining phases) excluding the nitrogen-containing phase 33 is a nitrogen-free phase 34, and the water The adsorption of vortex currents can be reliably prevented, and the generation of large water resistance in the surface or underwater moving body 27 (ship 27a, submarine 27b, underwater drone 27c) on which the inorganic coating film 10a (coating film 10) or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the surface 13 of the part in contact with water can be prevented, and the underwater movement speed of the surface or underwater moving body 27 (ship 27a, submarine 27b, underwater drone 27c) in water can be prevented from decreasing. Since the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b (coating film 10) formed on the surface 13 of the part in contact with water has excellent strength, the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b of the surface or underwater moving body 27 (ship 27a, submarine 27b, underwater drone 27c) can prevent the surface or underwater moving body 27 from being scratched by the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b. [Explanation of symbols]

[0217] 10 Coating film 10a Inorganic coating film 10b Organic / inorganic hybrid coating film 11 Composite materials 12 Base material (article) 13 Surface, peripheral surface (contact surface) 14 Coating fluid 15. Golf Clubs 16 Club Head 17 Shaft 18 Fishing Rod 19 Rod 20 Touch panel type digital signage (touch panel) 21 Touch panel display 22 Solar Cells 23 Front plate 24 Helmet 25 Rotating Body 25a Propeller 25b screw 26 Land or air vehicles 26a Automobiles (Racing cars) 26b Aircraft (passenger plane) 26c Train (Shinkansen) 26d Drone 26e Rocket 26f Bike (Racing Bike) 26g Bicycle (road bike) 27 Surface or underwater vehicles 27a Ship 27b submarine 27c Underwater drone 28 Surface layer 29 Covering layer 30 back layer 31 Middle Class 32 Anchor section 33 Nitrogen-containing phase 34 Nitrogen-free phase 35 Solar Cell Module 36 Frames 37 Protective Plate 38 Encapsulating materials 39 Solar Cells 40 Encapsulating material 41 Backplate 42 Shell 43 Shield 44 Chin strap 45 Ventilation

Claims

1. In the coating film formed on the substrate, The coating film contains silicon (Si) and oxygen (O) and is separated into two or more phases, A coating film characterized in that at least one of the phases is a nitrogen-containing phase that contains nitrogen (N).

2. 2. The coating film according to claim 1, wherein the ratio of the nitrogen-containing phase to the total area of ​​the coating film is 20% by area or more and 90% by area or less on the plane of the coating film.

3. 3. The coating film according to claim 2, wherein the ratio of the nitrogen-containing phase to the total area of ​​the coating film is 30 area % or more and 70 area % or less on the plane of the coating film.

4. 4. The coating film according to claim 1, wherein the nitrogen-containing phase extends in any direction in the coating film and is continuously connected.

5. 5. The coating film according to claim 4, wherein the remaining phases, excluding the nitrogen-containing phase, among the phases separated into two or more phases are nitrogen-free phases, and the nitrogen-free phases extend in any direction in the coating film and are separated from each other.

6. 6. The coating film according to claim 5, wherein the electrical resistance of the nitrogen-containing phase is smaller than that of the nitrogen-free phase.

7. The coating film according to claim 6, wherein the average thickness of the coating film is 0.2 μm or more and 20 μm or less.

8. 8. The coating film according to claim 7, wherein the electrical resistance of the coating film is smaller than that of a contact surface of the substrate on which the coating film is formed.

9. The coating film according to claim 8, wherein the contact surface of the substrate is made of any one of a resin, a material containing a resin, glass, and a metal.

10. The coating film according to claim 9 , which is either a glass-based inorganic coating film or a glass-based organic / inorganic hybrid coating film.

11. A composite material comprising a substrate and the coating film according to any one of claims 1 to 10 formed on the contact surface of the substrate.

12. The composite material according to claim 11, wherein the contact surface of the substrate on which the coating film is formed is insulating.

13. 13. The composite material according to claim 11 or 12, wherein the contact surface of the substrate on which the coating film is formed is made of any one of a resin, a material containing a resin, glass, and a metal.

14. 11. A golf club comprising the coating film according to claim 1 formed on at least one of the club head and shaft of the golf club.

15. A fishing rod comprising the coating film according to any one of claims 1 to 10 formed on the rod.

16. A touch panel comprising a coating film according to any one of claims 1 to 10 formed on a touch panel display.

17. A solar cell panel comprising the coating film according to any one of claims 1 to 10 formed on a front panel of the solar cell panel.

18. A helmet, comprising the coating film according to any one of claims 1 to 10 formed on a surface of the helmet.

19. A rotating body, comprising a propeller, a rotor, a screw, or a blade having a surface on which the coating film according to any one of claims 1 to 10 is formed.

20. A moving body comprising a coating film according to any one of claims 1 to 10 formed on a surface in contact with air of an automobile, an airplane, a train, a drone, a rocket, a motorcycle, or a bicycle, or formed on a surface in contact with water of a ship, a submarine, or an underwater drone.

Citation Information

Patent Citations

  • Golf club

    JP2019051291A

  • Coating liquid and coating method

    JP2021014514A